Manufacturing method of structure, and structure
By employing a transparent base material with a light-shielding pattern and negative photosensitive resin, the method addresses shape abnormalities in conductive patterns, achieving precise and stable conductive patterns through controlled exposure and development.
Patent Information
- Application Number
- JP2022518063
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-04-30
- Filing Date
- 2021-04-26
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2041-04-26
AI Technical Summary
Conventional methods for forming conductive patterns, such as the subtractive and semi-additive methods, suffer from shape abnormalities like tapered shapes due to cracking, peeling, chipping, or side etching, and dimensional fluctuations, making it difficult to achieve stable and precise conductive patterns.
A method involving a transparent base material with a light-shielding pattern and a negative photosensitive resin is used, where a laminate is prepared, exposed to light, developed, and then a pattern is formed, utilizing a light-shielding pattern as a mold to reduce shape abnormalities.
The method effectively reduces the occurrence of shape abnormalities in conductive patterns, enabling the formation of precise and stable patterns with improved control over shape and dimensions.
Smart Images

Figure 0007607646000011 
Figure 0007607646000012 
Figure 0007607646000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a method for manufacturing a structure and a structure. [Background technology]
[0002] Conductive patterns such as thin metal wires are used in various applications. Examples of applications of conductive patterns include touch sensors of touch panels, antennas, fingerprint authentication parts, foldable devices, and transparent FPCs (Flexible Printed Circuits). For example, in the manufacture of semiconductor packages, printed wiring boards, and rewiring layers of interposers, fine conductive patterns are formed on substrates. For example, films, sheets, metal substrates, ceramic substrates, or glass are used as substrates.
[0003] As a general method for forming a conductive pattern, for example, a subtractive method and a semi-additive method are known (for example, Patent Document 1 and Patent Document 2). In the subtractive method, for example, a conductive layer on a substrate is protected with a resist pattern, and then the conductive layer not protected by the resist pattern is removed by etching, thereby forming a conductive pattern. On the other hand, in the semi-additive method, for example, an electroless copper plating layer called a seed layer is provided on a substrate, and then a resist pattern is further provided on the electroless copper plating layer. Next, a conductive pattern is formed by plating on the electroless copper plating layer on which the resist pattern is not provided, and then the unnecessary resist pattern and the electroless copper plating layer (seed layer) are removed.
[0004] Patent Document 1: JP 2015-225650 A Patent Document 2: JP 2015-065376 A Summary of the Invention [Problem to be solved by the invention]
[0005] For example, a thick conductive pattern may be formed to reduce the electrical resistance of the conductive pattern. However, in the subtractive method, the conductive layer protected by the resist pattern may also be eroded by the chemical solution due to a phenomenon in which etching proceeds isotropically in the in-plane direction of the substrate on which the conductive layer is arranged (for example, referred to as "side etching"). The occurrence of side etching affects the form (for example, shape and dimensions) of the conductive pattern formed through etching, so that, for example, it may be difficult to form a rectangular conductive pattern. In the semi-additive method, the formation of the conductive pattern becomes unstable due to the adhesion between the seed layer and the resist pattern, which is an issue. In addition, the semi-additive method also has the same issues as the subtractive method, since a part of the conductive pattern may be removed when removing an unnecessary seed layer.
[0006] The present disclosure has been made in consideration of the above circumstances. The problem to be solved by one embodiment of the present disclosure is to provide a method for manufacturing a structure having a pattern in which the occurrence of morphological abnormalities (such as cracking, peeling, chipping, or the occurrence of tapered shapes due to side etching, or dimensional fluctuations due to etching variations; the same applies below) is reduced. Another problem to be solved by another embodiment of the present disclosure is to provide a structure having a pattern with reduced occurrence of morphological anomalies. [Means for solving the problem]
[0007] Means for solving the above problems include the following aspects. <1> The method for producing a structure includes the steps of: preparing a laminate having a transparent substrate, a light-shielding pattern 1 disposed on the transparent substrate, and a negative-type photosensitive resin layer N disposed on the transparent substrate and the light-shielding pattern 1 and in contact with the transparent substrate; irradiating light onto a portion of the negative-type photosensitive resin layer N from the surface of the transparent substrate opposite to the surface on which the light-shielding pattern 1 is disposed; developing the negative-type photosensitive resin layer N irradiated with light to form a resin pattern 2 on the transparent substrate; and forming a pattern 3 in an area defined by the light-shielding pattern 1 and the resin pattern 2, wherein the resulting structure has the resin pattern 2 as a permanent film. <2> The light-shielding pattern 1 contains a metal. <1> A method for producing the structure described in claim 1. <3> The pattern 3 has electrical conductivity. <1> or <2> A method for producing the structure described in claim 1. <4> The pattern 3 is a pattern formed by a plating method. <1> ~ <3> 13. A method for producing the structure according to any one of the preceding claims. <5> The light-shielding pattern 1 and the pattern 3 contain the same kind of material. <1> ~ <4> 13. A method for producing the structure according to any one of the preceding claims. <6> The negative photosensitive resin layer N contains an alkali-soluble polymer, an ethylenically unsaturated compound, and a photopolymerization initiator. <1> ~ <5> 13. A method for producing the structure according to any one of the preceding claims. <7> The above ethylenically unsaturated compound includes a tri- or higher functional ethylenically unsaturated compound. <6> A method for producing the structure described in claim 1. <8> The ethylenically unsaturated compound includes a di(meth)acrylate compound having a dicyclopentanyl structure or a dicyclopentenyl structure. <6> or <7> A method for producing the structure described in claim 1. <9> The negative photosensitive resin layer N contains a multifunctional epoxy resin, a hydroxyl group-containing compound, and a photocationic polymerization initiator. <1> ~ <5> 13. A method for producing the structure according to any one of the preceding claims. <10> The negative photosensitive resin layer N contains a metal oxidation inhibitor. <1> ~ <9> 13. A method for producing the structure according to any one of the preceding claims. <11> The method further includes a step of forming a light-shielding layer on one surface of a transparent substrate, a step of forming a photoresist layer on the light-shielding layer, a step of exposing and developing the photoresist layer to form a resist pattern, and a step of etching the light-shielding layer to form the light-shielding pattern 1. <1> ~ <10> 13. A method for producing the structure according to any one of the preceding claims. <12> The average thickness of the light-shielding pattern 1 is greater than the average thickness of the light-shielding pattern 3. <1> ~ <11> 13. A method for producing the structure according to any one of the preceding claims. <13> The transparent substrate is a transparent film substrate. <1> ~ <12> 13. A method for producing the structure according to any one of the preceding claims. <14> The method further includes a step of performing at least one of post-exposure and post-heating on the resin pattern 2. <1> ~ <13> 13. A method for producing the structure according to any one of the preceding claims. <15> The negative photosensitive resin layer N is a layer formed from a photosensitive transfer material. <1> ~ <14> 13. A method for producing the structure according to any one of the preceding claims. <16> The resulting structure is one selected from the group consisting of a touch sensor, an electromagnetic shield, an antenna, a wiring board, a conductive heating element, and a viewing angle control film. <1> ~ <15> 13. A method for producing the structure according to any one of the preceding claims. <17> A structure comprising a transparent substrate, a light-shielding pattern 1 disposed on the transparent substrate, a resin pattern 2 disposed adjacent to the light-shielding pattern 1 on the transparent substrate and in contact with the transparent substrate, and a pattern 3 in a region defined by the light-shielding pattern 1 and the resin pattern 2, wherein the light-shielding pattern 1 has an average thickness of 2 μm or less, the resin pattern 2 has an average thickness of more than 2 μm, the average thickness of the pattern 3 is greater than the average thickness of the light-shielding pattern 1, and the resin pattern 2 is a permanent film. Effect of the Invention
[0008] According to an embodiment of the present disclosure, it is possible to provide a method for manufacturing a structure having a pattern with reduced occurrence of morphological abnormalities. Furthermore, according to another embodiment of the present disclosure, a structure having a pattern with reduced occurrence of morphological anomalies can be provided. [Brief description of the drawings]
[0009] [Figure 1] 1 is a schematic cross-sectional view showing an example of a method for producing a structure according to the present disclosure. [Diagram 2] 1 is a schematic cross-sectional view showing an example of a structure according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The present disclosure will be described below with reference to the accompanying drawings, in which reference numerals may be omitted. In addition, in this specification, a numerical range expressed using "to" means a range that includes the numerical values before and after "to" as the lower limit and upper limit. In addition, in this specification, "(meth)acrylic" refers to both or either of acrylic and methacrylic, and "(meth)acrylate" refers to both or either of acrylate and methacrylate. Furthermore, in this specification, when a plurality of substances corresponding to each component are present in the composition, the amount of each component in the composition means the total amount of the corresponding substances present in the composition, unless otherwise specified. In this specification, the term "process" includes not only an independent process but also a process that cannot be clearly distinguished from other processes as long as the intended purpose of the process is achieved. In the description of groups (atomic groups) in this specification, when there is no indication of substituted or unsubstituted, the term encompasses both unsubstituted and substituted groups. For example, the term "alkyl group" encompasses not only alkyl groups without a substituent (unsubstituted alkyl groups) but also alkyl groups with a substituent (substituted alkyl groups). In this specification, unless otherwise specified, "exposure" includes not only exposure using light, but also drawing using particle beams such as electron beams and ion beams. In addition, examples of light used for exposure generally include the bright line spectrum of a mercury lamp, far ultraviolet light represented by an excimer laser, extreme ultraviolet light (EUV light), X-rays, electron beams, and other actinic rays (active energy rays). In addition, chemical structural formulas in this specification may be described as simplified structural formulas in which hydrogen atoms are omitted. In the present disclosure, "mass %" and "weight %" are synonymous, and "parts by mass" and "parts by weight" are synonymous. Also, in the present disclosure, combinations of two or more preferred aspects are more preferred aspects. In addition, unless otherwise specified, the weight average molecular weight (Mw) and number average molecular weight (Mn) in the present disclosure are molecular weights detected by a gel permeation chromatography (GPC) analyzer using columns of TSKgel GMHxL, TSKgel G4000HxL, or TSKgel G2000HxL (all product names manufactured by Tosoh Corporation) in a solvent of THF (tetrahydrofuran) and a differential refractometer, and converted using polystyrene as a standard substance. In the present disclosure, "alkali-soluble" means a property in which the solubility in an aqueous solution of sodium carbonate (100 g, sodium carbonate concentration: 1 mass %) at a liquid temperature of 22°C is 0.1 g or more. In the present disclosure, "electrical conductivity" refers to the property of allowing electric current to flow easily. The required ease of electric current flow is not limited, and may be to a degree necessary for the purpose and application. When the electrical conductivity is expressed as a volume resistivity, the volume resistivity is 1×10 6 Preferably less than 1×10 4 It is more preferable that it is less than Ωcm. In the present disclosure, "light" refers to electromagnetic waves including ultraviolet light, visible light, and infrared light. The light is preferably light having a wavelength within a range of 200 nm to 1,500 nm, more preferably light having a wavelength within a range of 250 nm to 450 nm, and particularly preferably light having a wavelength within a range of 300 nm to 410 nm. In this disclosure, the term "solid content" refers to all components of a target object excluding the solvent.
[0011] (Method of Manufacturing Structure) A method for producing a structure according to the present disclosure includes the steps of preparing a laminate having a transparent substrate, a light-shielding pattern 1 disposed on the transparent substrate, and a negative photosensitive resin layer N disposed on the transparent substrate and the light-shielding pattern 1 and in contact with the transparent substrate (hereinafter also referred to as a "preparation step"); irradiating a part of the negative photosensitive resin layer N with light from the surface of the transparent substrate opposite to the surface on which the light-shielding pattern 1 is provided (hereinafter also referred to as an "exposure step"); forming a resin pattern 2 on the transparent substrate by developing the negative photosensitive resin layer N irradiated with light (hereinafter also referred to as a "development step"); and forming a pattern 3 in a region defined by the light-shielding pattern 1 and the resin pattern 2 (hereinafter also referred to as a "pattern 3 formation step"); and the obtained structure has the resin pattern 2 as a permanent film.
[0012] The reason why the method for manufacturing a structure according to the present disclosure exhibits the above-mentioned effects is believed to be as follows. As described above, the present inventors have found that in conventional methods for manufacturing a structure (for example, subtractive methods and semi-additive methods), there are cases where the controllability of the shape and dimensions of a pattern is insufficient. On the other hand, in the method for manufacturing a structure according to the present disclosure, by including the above-mentioned steps, it is possible to reduce the occurrence of pattern morphology abnormalities that accompany, for example, side etching or removal of the seed layer. Here, a method for producing a structure according to the present disclosure will be described with reference to FIG. Fig. 1 is a schematic cross-sectional view showing an example of a method for producing a structure according to the present disclosure. Fig. 1(a) shows an example of a preparation step. Fig. 1(b) shows an example of an exposure step. Fig. 1(c) shows an example of a development step. Fig. 1(d) shows an example of a pattern 3 formation step. The laminate 100 shown in FIG. 1(a) has a transparent substrate 10, a light-shielding pattern 20 (light-shielding pattern 1), and a negative photosensitive resin layer 30 (negative photosensitive resin layer N). As shown in FIG. 1(b), light is irradiated onto the surface of the transparent substrate 10 opposite to the surface facing the light-shielding pattern 20 (i.e., the exposed surface 10a). Since the proportion of light passing through the light-shielding pattern 20 is small, the light incident on the exposed surface 10a of the transparent substrate 10 passes through the transparent substrate 10 and the exposed portion 30a of the negative photosensitive resin layer 30. As a result, the exposed portion 30a of the negative photosensitive resin layer 30 is selectively exposed. As shown in FIG. 1(c), the negative photosensitive resin layer 30 is developed to remove the portions of the negative photosensitive resin layer 30 other than the exposed portion 30a, and a resin pattern 40 (resin pattern 2) is formed in the region (i.e., the groove) defined by the transparent substrate 10 and the light-shielding pattern 20. As shown in FIG. 1(d), a pattern 50 (pattern 3) is formed on the light-shielding pattern 20. In FIG. 1(d), the pattern 50 is formed in the region (i.e., the groove) defined by the light-shielding pattern 20 that functions like a mold and the resin pattern 40. By going through the above-mentioned steps, the pattern 50 can be easily formed. Therefore, according to the method for producing a structure according to the present disclosure, a pattern (preferably a conductive pattern) in which the occurrence of morphological abnormalities is reduced is formed.
[0013] In the method for producing a structure according to the present disclosure, the obtained structure has the resin pattern 2 as a permanent film. In the present disclosure, the term "permanent film" refers to a film (layer) that remains even after completion of an article having the above structure (including a product, and also including a case where the above structure itself is an article). Specific examples of permanent films include an insulating film, a protective film, a spacer, and the like. The structure obtained by the method for producing a structure according to the present disclosure is preferably one type of structure selected from the group consisting of a touch sensor, an electromagnetic wave shield, an antenna, a wiring board, a conductive heating element, and a viewing angle control film.
[0014] <Preparation process> The manufacturing method of the laminate according to the present disclosure includes a step of preparing a laminate having a transparent substrate, a light-shielding pattern 1 arranged on the transparent substrate, and a negative-type photosensitive resin layer N arranged on the transparent substrate and the light-shielding pattern 1 and in contact with the transparent substrate (preparation step). In the present disclosure, "preparation" means making an object ready for use. The laminate may be a laminate manufactured in advance. The laminate may be a laminate manufactured in a preparation step. That is, the preparation step may include a step of manufacturing the laminate.
[0015] [Transparent base material] The laminate has a transparent substrate. In the present disclosure, "transparent" means that the transmittance of the exposure wavelength in the above-mentioned exposure step is 50% or more. The transmittance of the exposure wavelength defined in the term "transparent" is preferably 80% or more, more preferably 90%, and particularly preferably 95%. In the present disclosure, "transmittance of the exposure wavelength" means the transmittance of the wavelength contained in the light that reaches the object (e.g., transparent substrate) in the exposure step. For example, when a light source including a wavelength of 365 nm is used in the exposure step, "transmittance of the exposure wavelength" refers to the transmittance of the wavelength of 365 nm. In the present disclosure, "transmittance" is the ratio of the intensity of the emitted light that passes through the object to the intensity of the incident light when the light is incident in a direction perpendicular to the main surface of the object to be measured (i.e., in the thickness direction). The transmittance is measured using the MCPD Series manufactured by Otsuka Electronics Co., Ltd. Moreover, the transparent base material preferably has a transmittance of 80% or more for light with a wavelength of 400 nm to 700 nm.
[0016] The shape of the transparent substrate is not limited. For example, a film-like or plate-like transparent substrate is preferably used as the transparent substrate. Among them, the transparent substrate is preferably a transparent film substrate.
[0017] Examples of the transparent substrate include a resin substrate (e.g., a resin film) and a glass substrate. The resin substrate is preferably a resin substrate that transmits visible light. Examples of preferred components of the resin substrate that transmits visible light include polyamide resins, polyethylene terephthalate resins, polyethylene naphthalate resins, cycloolefin resins, polyimide resins, and polycarbonate resins. Examples of more preferred components of the resin substrate that transmits visible light include polyamide, polyethylene terephthalate (PET), cycloolefin polymer (COP), polyethylene naphthalate (PEN), polyimide, and polycarbonate. The transparent substrate is preferably a polyamide film, a polyethylene terephthalate film, a cycloolefin polymer (COP), a polyethylene naphthalate film, a polyimide film, or a polycarbonate film, and more preferably a polyethylene terephthalate film.
[0018] Examples of the transparent substrate include paper phenol, paper epoxy, glass composite, glass epoxy, polytetrafluoroethylene, and rigid-flexible materials obtained by combining a hard material and a soft material. The transparent substrate may be a porous transparent substrate. The transparent substrate may include a filler and an additive.
[0019] The surface of the transparent substrate may be modified, for example, by alkali treatment or energy ray irradiation.
[0020] The transparent substrate may have a single-layer structure or a multi-layer structure. The transparent substrate may include, for example, a functional layer. Examples of the functional layer include an adhesive layer, a hard coat layer, and a refractive index adjustment layer.
[0021] The thickness of the transparent substrate is not limited. The thickness of the transparent substrate is preferably in the range of 10 μm to 200 μm, more preferably in the range of 20 μm to 120 μm, and particularly preferably in the range of 20 μm to 100 μm. The thickness of the transparent substrate is measured by the following method. A scanning electron microscope (SEM) is used to observe a cross section of the transparent substrate in a direction perpendicular to the main surface (i.e., in the thickness direction). Based on the obtained observation image, the thickness of the transparent substrate is measured at 10 points. The measured values are arithmetically averaged to obtain the average thickness of the transparent substrate.
[0022] The total light transmittance of the transparent substrate is preferably high. The total light transmittance of the transparent substrate is preferably 50% or more, more preferably 80% or more, even more preferably 90% or more, and particularly preferably 95% or more. There is no upper limit to the total light transmittance of the transparent substrate. The total light transmittance of the transparent substrate may be determined to be in the range of 100% or less. The total light transmittance is measured by the method specified in JIS K 7361-1 (1997).
[0023] [Light-blocking pattern] The laminate has a light-shielding pattern 1 on a transparent substrate. For example, as shown in FIG. 1(b), when the laminate has the light-shielding pattern 1, a part of the negative photosensitive resin layer can be selectively exposed in the exposure step. In the present disclosure, "light-shielding" means that the transmittance of the exposure wavelength is less than 50%. The transmittance of the exposure wavelength defined in the term "light-shielding" is preferably less than 30%, more preferably less than 10%, and particularly preferably less than 1%. Moreover, the light-shielding pattern 1 preferably has a transmittance of less than 30% for light having a wavelength of 400 nm to 700 nm.
[0024] The light-shielding pattern 1 is preferably conductive. The light-shielding pattern 1 having conductivity can function as an electric conductor (e.g., a seed layer) when plating is performed in the pattern 3 forming step described later. The seed layer can function as a cathode in electroplating, for example. In particular, it is preferable that the light-shielding pattern 1 contains a metal.
[0025] Examples of the components of the light-shielding pattern 1 include metals. Examples of the metals include Nb (niobium), Al (aluminum), Ni (nickel), Zn (zinc), Mo (molybdenum), Ta (tantalum), Ti (titanium), V (vanadium), Cr (chromium), Fe (iron), Co (cobalt), W (tungsten), Cu (copper), Sn (tin), and Mn (manganese). From the viewpoint of electrical conductivity, the light-shielding pattern 1 preferably contains a metal, more preferably contains at least one metal selected from the group consisting of Nb, Al, Ni, Zn, Mo, Ta, Ti, V, Cr, Fe, Co, W, Cu, Sn, and Mn, and particularly preferably contains Cu. Cu is preferable from the viewpoint of low electrical resistance and low cost. The light-shielding pattern 1 may contain one type of metal alone, or two or more types of metals. The metal contained in the light-shielding pattern 1 may be a single metal or an alloy. The light-shielding pattern 1 preferably contains Cu or a Cu alloy. When the light-shielding pattern 1 contains a metal, the metal element contained in the light-shielding pattern may be the same as or different from the metal element contained in the conductive pattern described below. The light-shielding pattern 1 preferably contains the same metal element as the metal element contained in the conductive pattern.
[0026] The light-shielding pattern 1 may contain elements other than metal elements. Examples of elements other than metal elements include C (carbon), P (phosphorus), and B (boron). Elements other than metal elements may form alloys with metal elements.
[0027] There are no limitations on the shape of the light-shielding pattern 1. The shape of the light-shielding pattern 1 may be determined according to, for example, the shape of the intended conductive pattern.
[0028] The light-shielding pattern 1 may have a single-layer structure or a multi-layer structure. The components of each layer of the light-shielding pattern 1 having a multi-layer structure may be the same or different.
[0029] The thickness of the light-shielding pattern 1 is not limited. The average thickness of the light-shielding pattern 1 is preferably 3 μm or less, more preferably 2 μm or less, even more preferably 1 μm or less, and particularly preferably 0.5 μm or less. When the average thickness of the light-shielding pattern 1 is 3 μm or less, the moldability of the light-shielding pattern can be improved. As a result, the occurrence of morphological abnormalities in the conductive pattern can be further reduced. The average thickness of the light-shielding pattern 1 is preferably 0.05 μm or more, more preferably 0.1 μm or more, and particularly preferably 0.3 μm or more. When the average thickness of the light-shielding pattern 1 is 0.05 μm or more, the transmittance of the exposure wavelength can be reduced. In addition, when the light-shielding pattern 1 is used as a seed layer, the productivity of the conductive pattern can be improved. The average thickness of the light-shielding pattern 1 is measured by a method similar to the method for measuring the average thickness of the transparent substrate.
[0030] The width of the light-shielding pattern 1 is not limited. The width of the light-shielding pattern 1 is the length of the light-shielding pattern 1 in a direction perpendicular to the longitudinal direction of the light-shielding pattern 1 in the surface direction of the transparent substrate. For example, if the light-shielding pattern 1 is a line-and-space pattern, the width of the light-shielding pattern 1 is the length in the short direction of the line pattern. Also, for example, if the light-shielding pattern 1 has a circular or elliptical cross-sectional shape in the surface direction of the transparent substrate, the width of the light-shielding pattern 1 is the minimum diameter of the circular or elliptical shape. The width of the light-shielding pattern 1 may be determined, for example, according to the width of the conductive pattern formed in the pattern 3 forming step. The average width of the light-shielding pattern 1 is preferably 50 μm or less, more preferably 10 μm or less, even more preferably 5 μm or less, and particularly preferably 2 μm or less. The average width of the light-shielding pattern 1 is preferably 0.1 μm or more, more preferably 0.5 μm or more. The average width of the light-shielding pattern 1 is the arithmetic average of the widths of the light-shielding pattern measured at five points.
[0031] The light-shielding pattern 1 may be in contact with the transparent substrate directly or via another layer. Examples of the other layer include an adhesive layer. For example, the laminate may have an adhesive layer between the transparent substrate and the light-shielding pattern 1. The components of the adhesive layer are not limited. The components of the adhesive layer may be determined, for example, according to the adhesive strength between the transparent substrate and the light-shielding pattern 1 and the stability in the use environment (for example, humidity and temperature) of the conductive pattern obtained by the manufacturing method of the structure according to the present disclosure. The adhesive layer preferably contains at least one selected from Ni, Zn, Mo, Ta, Ti, V, Cr, Fe, Co, W, Cu, Sn, and Mn. The adhesive layer may further contain at least one selected from the group consisting of C (carbon atom), O (oxygen atom), H (hydrogen atom), and N (nitrogen atom). The adhesive layer may be a blackening layer. The blackening layer can suppress the reflection of light by the light-shielding pattern in the exposure step. When the adhesive layer is made to function as a blackening layer, the adhesive layer preferably contains, for example, a Ni-Cu alloy. The adhesive layer functioning as a blackening layer may further contain at least one selected from the group consisting of C, O, H, and N. The thickness of the adhesive layer is not limited. The average thickness of the adhesive layer is preferably 3 nm to 50 nm, more preferably 3 nm to 35 nm, and particularly preferably 3 nm to 33 nm.
[0032] [Negative photosensitive resin layer N] The laminate has a negative photosensitive resin layer N disposed on a transparent substrate and a light-shielding pattern 1 and in contact with the transparent substrate. The negative photosensitive resin layer N may be in contact with the light-shielding pattern 1 directly or via another layer. It is preferable that the negative photosensitive resin layer N is in contact with the light-shielding pattern 1. As the negative photosensitive resin layer N, a known negative photosensitive resin layer can be used.
[0033] In one embodiment, the negative photosensitive resin layer N preferably contains a polymer A described below, a polymerizable compound B described below, and a photopolymerization initiator. The negative photosensitive resin layer N preferably contains 10% by mass to 90% by mass of the polymer A, 5% by mass to 70% by mass of the polymerizable compound B, and 0.01% by mass to 20% by mass of the photopolymerization initiator, relative to the total mass of the negative photosensitive resin layer N. In one embodiment, the negative photosensitive resin layer N preferably contains an alkali-soluble polymer, an ethylenically unsaturated compound, and a photopolymerization initiator.
[0034] From the viewpoint of curability and developability, the negative photosensitive resin layer N preferably contains an alkali-soluble polymer, an ethylenically unsaturated compound, and a photoacid generator. Furthermore, from the viewpoint of the strength and durability of the resulting resin pattern 2 as a permanent film, the negative photosensitive resin layer N preferably contains a polyfunctional epoxy resin, a hydroxy group-containing compound, and a cationic polymerization initiator. The negative photosensitive resin layer N will be specifically described below.
[0035] -Alkali-soluble polymer- The negative photosensitive resin layer N preferably contains an alkali-soluble polymer. In this disclosure, "alkali-soluble" means that the solubility in 100 g of a 1% by mass aqueous solution of sodium carbonate at 22°C is 0.1 g or more. From the viewpoint of developability, the alkali-soluble polymer preferably has an acid value of 60 mgKOH / g or more. Furthermore, from the viewpoint of easily forming a strong film by thermally crosslinking with the crosslinking component by heating, the alkali-soluble polymer is more preferably a resin having a carboxy group with an acid value of 60 mgKOH / g or more (so-called carboxy group-containing resin), and particularly preferably an acrylic resin having a carboxy group with an acid value of 60 mgKOH / g or more (so-called carboxy group-containing acrylic resin). In the present disclosure, acrylic resin refers to a resin having a structural unit derived from a (meth)acrylic compound, and the content of the structural unit is preferably 30 mass% or more, and more preferably 50 mass% or more, relative to the total mass of the resin. When the alkali-soluble polymer is a resin having a carboxy group, the three-dimensional crosslinking density can be increased by, for example, adding a thermally crosslinkable compound such as a blocked isocyanate compound to thermally crosslink the resin. In addition, when the carboxy group of the resin having a carboxy group is dehydrated and hydrophobized, the humidity and heat resistance can be improved.
[0036] The carboxyl group-containing acrylic resin having an acid value of 60 mgKOH / g or more is not particularly limited as long as it satisfies the above-mentioned acid value condition, and can be appropriately selected from known acrylic resins. For example, among the polymers described in paragraph 0025 of JP-A-2011-95716, carboxyl group-containing acrylic resins having an acid value of 60 mgKOH / g or more, and among the polymers described in paragraphs 0033 to 0052 of JP-A-2010-237589, carboxyl group-containing acrylic resins having an acid value of 60 mgKOH / g or more can be preferably used.
[0037] From the viewpoints of suppression of development residues, moisture permeability of the resulting cured film, and adhesion of the resulting uncured film, the alkali-soluble polymer is preferably an acrylic resin or a styrene-acrylic copolymer, and more preferably a styrene-acrylic copolymer. In the present disclosure, a styrene-acrylic copolymer refers to a resin having a structural unit derived from a styrene compound and a structural unit derived from a (meth)acrylic compound, and the total content of the structural units derived from the styrene compound and the structural units derived from the (meth)acrylic compound is preferably 30 mass% or more, and more preferably 50 mass% or more, relative to the total mass of the copolymer. Furthermore, the content of the structural units derived from a styrene compound is preferably 1% by mass or more, more preferably 5% by mass or more, and particularly preferably 5% by mass or more and 80% by mass or less, based on the total mass of the copolymer. In addition, the content of the structural units derived from the (meth)acrylic compound is preferably 5% by mass or more, more preferably 10% by mass or more, and particularly preferably 20% by mass or more and 95% by mass or less, based on the total mass of the copolymer. Furthermore, the (meth)acrylic compound may include a (meth)acrylate compound, (meth)acrylic acid, a (meth)acrylamide compound, (meth)acrylonitrile, etc. Among them, at least one compound selected from the group consisting of a (meth)acrylate compound and (meth)acrylic acid is preferred.
[0038] <<Polymer A>> The negative photosensitive resin layer N preferably contains a polymer A. The polymer A is preferably an alkali-soluble polymer. The alkali-soluble polymer includes polymers that are easily soluble in alkaline substances. In the present disclosure, "alkali-soluble" means that the solubility in 100 g of a 1% by mass aqueous solution of sodium carbonate at 22°C is 0.1 g or more.
[0039] The acid value of the polymer A is preferably 220 mgKOH / g or less, more preferably less than 200 mgKOH / g, and particularly preferably less than 190 mgKOH / g, from the viewpoint of more excellent resolution by suppressing swelling of the negative photosensitive resin layer N by the developer. The lower limit of the acid value is not limited. The acid value of the polymer A is preferably 60 mgKOH / g or more, more preferably 120 mgKOH / g or more, even more preferably 150 mgKOH / g or more, and particularly preferably 170 mgKOH / g or more, from the viewpoint of more excellent developability. The acid value of the polymer A can be adjusted, for example, by the type of structural unit constituting the polymer A and the content of the structural unit containing an acid group.
[0040] In this disclosure, the acid value is the mass (mg) of potassium hydroxide required to neutralize 1 g of a sample. In this disclosure, the unit of the acid value is written as mgKOH / g. The acid value can be calculated, for example, from the average content of acid groups in a compound.
[0041] The weight average molecular weight (Mw) of the polymer A is preferably 5,000 to 500,000. The weight average molecular weight of 500,000 or less is preferable from the viewpoint of improving resolution and developability. The weight average molecular weight of the polymer A is more preferably 100,000 or less, further preferably 60,000 or less, and particularly preferably 50,000 or less. On the other hand, the weight average molecular weight of 5,000 or more is preferable from the viewpoint of controlling the properties of the development aggregate. The weight average molecular weight of the polymer A is more preferably 10,000 or more, further preferably 20,000 or more, and particularly preferably 30,000 or more.
[0042] The dispersity of polymer A is preferably 1.0 to 6.0, more preferably 1.0 to 5.0, further preferably 1.0 to 4.0, and particularly preferably 1.0 to 3.0. In the present disclosure, the dispersity is the ratio of the weight average molecular weight to the number average molecular weight (weight average molecular weight / number average molecular weight).
[0043] From the viewpoint of suppressing line width increase and deterioration of resolution when the focal position is shifted during exposure, polymer A preferably has a structural unit having an aromatic hydrocarbon group, and more preferably has a structural unit derived from a monomer having an aromatic hydrocarbon group.
[0044] Examples of the aromatic hydrocarbon group include a substituted or unsubstituted phenyl group and a substituted or unsubstituted aralkyl group.
[0045] The content ratio of the structural unit derived from the monomer having an aromatic hydrocarbon group in the polymer A is preferably 20% by mass or more, more preferably 30% by mass or more, even more preferably 40% by mass or more, particularly preferably 45% by mass or more, and most preferably 50% by mass or more, based on the total mass of the polymer A. The upper limit of the content ratio of the structural unit derived from the monomer having an aromatic hydrocarbon group is not limited. The content ratio of the structural unit derived from the monomer having an aromatic hydrocarbon group in the polymer A is preferably 95% by mass or less, more preferably 85% by mass or less, based on the total mass of the polymer A. When the negative photosensitive resin layer contains multiple types of polymer A, the content ratio of the structural unit derived from the monomer having an aromatic hydrocarbon group is calculated as a weight average value.
[0046] Examples of the monomer having an aromatic hydrocarbon group include a monomer having an aralkyl group, styrene, and polymerizable styrene derivatives (e.g., methylstyrene, vinyltoluene, tert-butoxystyrene, acetoxystyrene, 4-vinylbenzoic acid, styrene dimer, and styrene trimer). The monomer having an aromatic hydrocarbon group is preferably a monomer having an aralkyl group or styrene.
[0047] Examples of the aralkyl group include a substituted or unsubstituted phenylalkyl group (excluding a benzyl group) and a substituted or unsubstituted benzyl group, with a substituted or unsubstituted benzyl group being preferred.
[0048] An example of a monomer having a phenylalkyl group is phenylethyl (meth)acrylate.
[0049] Examples of the monomer having a benzyl group include (meth)acrylates having a benzyl group (e.g., benzyl (meth)acrylate and chlorobenzyl (meth)acrylate) and vinyl monomers having a benzyl group (e.g., vinylbenzyl chloride and vinylbenzyl alcohol). The monomer having a benzyl group is preferably benzyl (meth)acrylate.
[0050] In one embodiment, when the structural unit derived from a monomer having an aromatic hydrocarbon group in polymer A is a structural unit derived from benzyl (meth)acrylate, the content of the structural unit derived from the benzyl (meth)acrylate monomer in polymer A is preferably 50% by mass to 95% by mass, more preferably 60% by mass to 90% by mass, even more preferably 70% by mass to 90% by mass, and particularly preferably 75% by mass to 90% by mass, relative to the total mass of polymer A.
[0051] In one embodiment, when the structural unit derived from a monomer having an aromatic hydrocarbon group in polymer A is a structural unit derived from styrene, the content of the structural unit derived from styrene in polymer A is preferably 20 mass% to 55 mass%, more preferably 25 to 45 mass%, even more preferably 30 mass% to 40 mass%, and particularly preferably 30 mass% to 35 mass%, relative to the total mass of polymer A.
[0052] In one embodiment, the polymer A having a structural unit derived from a monomer having an aromatic hydrocarbon group is preferably a copolymer obtained by polymerizing a monomer having an aromatic hydrocarbon group with at least one monomer selected from the group consisting of a first monomer described below and a second monomer described below. The copolymer has a structural unit derived from a monomer having an aromatic hydrocarbon group, and at least one monomer selected from the group consisting of a structural unit derived from the first monomer and a structural unit derived from the second monomer.
[0053] The polymer A may be a polymer that does not have a structural unit derived from a monomer having an aromatic hydrocarbon group. The polymer A that does not have a structural unit derived from a monomer having an aromatic hydrocarbon group is preferably a polymer obtained by polymerizing at least one type of a first monomer (excluding a monomer having an aromatic hydrocarbon group) described later, and more preferably a copolymer obtained by polymerizing at least one type of a first monomer (excluding a monomer having an aromatic hydrocarbon group) described later and at least one type of a second monomer (excluding a monomer having an aromatic hydrocarbon group) described later.
[0054] In one embodiment, the polymer A is preferably a polymer obtained by polymerizing at least one type of a first monomer described later, and more preferably a copolymer obtained by polymerizing at least one type of a first monomer described later and at least one type of a second monomer described later. The copolymer has a constitutional unit derived from the first monomer and a constitutional unit derived from the second monomer.
[0055] The first monomer is a monomer having a carboxy group and a polymerizable unsaturated group in the molecule. The first monomer may be a monomer having no aromatic hydrocarbon group in the molecule. Examples of the first monomer include (meth)acrylic acid, fumaric acid, cinnamic acid, crotonic acid, itaconic acid, 4-vinylbenzoic acid, maleic anhydride, and maleic acid half ester. The first monomer is preferably (meth)acrylic acid.
[0056] The content ratio of the structural unit derived from the first monomer in polymer A is preferably 5% by mass to 50% by mass, more preferably 10% by mass to 40% by mass, and particularly preferably 15% by mass to 30% by mass, relative to the total mass of polymer A.
[0057] The second monomer is a monomer that is non-acidic and has at least one polymerizable unsaturated group in the molecule. The second monomer may be a monomer that does not have an aromatic hydrocarbon group in the molecule. Examples of the second monomer include (meth)acrylate compounds, vinyl alcohol ester compounds, and (meth)acrylonitrile. In the present disclosure, "(meth)acrylonitrile" includes acrylonitrile, methacrylonitrile, or both acrylonitrile and methacrylonitrile.
[0058] Examples of (meth)acrylate compounds include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, cyclohexyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. The (meth)acrylate compound may include those having an alicyclic alkyl group, a straight-chain alkyl group, or a branched alkyl group.
[0059] An example of the vinyl alcohol ester compound is vinyl acetate.
[0060] The second monomer is preferably at least one selected from the group consisting of methyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and n-butyl (meth)acrylate, and is more preferably methyl (meth)acrylate.
[0061] The content ratio of the structural units derived from the second monomer in polymer A is preferably 5% by mass to 60% by mass, more preferably 15% by mass to 50% by mass, and particularly preferably 20% by mass to 45% by mass, relative to the total mass of polymer A.
[0062] From the viewpoint of suppressing line width thickening and deterioration of resolution when the focal position is shifted during exposure, the polymer A preferably contains at least one selected from the group consisting of a structural unit derived from a monomer having an aralkyl group and a structural unit derived from styrene. For example, the polymer A is preferably at least one selected from the group consisting of a copolymer containing a structural unit derived from methacrylic acid, a structural unit derived from benzyl methacrylate, and a structural unit derived from styrene, and a copolymer containing a structural unit derived from methacrylic acid, a structural unit derived from methyl methacrylate, a structural unit derived from benzyl methacrylate, and a structural unit derived from styrene.
[0063] In one embodiment, polymer A is preferably a polymer containing 25% to 60% by mass of structural units derived from a monomer having an aromatic hydrocarbon group, 20% to 55% by mass of structural units derived from a first monomer, and 20% to 55% by mass of structural units derived from a second monomer. Polymer A is more preferably a polymer containing 25% to 40% by mass of structural units derived from a monomer having an aromatic hydrocarbon group, 20% to 35% by mass of structural units derived from the first monomer, and 30% to 45% by mass of structural units derived from the second monomer.
[0064] In one embodiment, polymer A is preferably a polymer containing 70% by mass to 90% by mass of structural units derived from a monomer having an aromatic hydrocarbon group, and 10% by mass to 25% by mass of structural units derived from a first monomer.
[0065] The glass transition temperature (Tg) of the polymer A is preferably 30°C to 135°C. In the negative photosensitive resin layer, when the Tg of the polymer A is 135°C or less, it is possible to suppress line width thickening and deterioration of resolution when the focal position is shifted during exposure. From the above viewpoint, the Tg of the polymer A is more preferably 130°C or less, further preferably 120°C or less, and particularly preferably 110°C or less. In addition, it is preferable that the Tg of the polymer A is 30°C or more from the viewpoint of improving edge fuse resistance. From the above viewpoint, the Tg of the polymer A is more preferably 40°C or more, further preferably 50°C or more, particularly preferably 60°C or more, and most preferably 70°C or more.
[0066] The polymer A may be a commercially available product or a synthetic product. The synthesis of the polymer A is preferably carried out, for example, by adding an appropriate amount of a radical polymerization initiator (e.g., benzoyl peroxide or azoisobutyronitrile) to a solution obtained by diluting at least one of the above-mentioned monomers with a solvent (e.g., acetone, methyl ethyl ketone, or isopropanol), and then heating and stirring. The synthesis may also be carried out while dropping a part of the mixture into the reaction solution. After the reaction is completed, further solvent may be added to adjust the concentration to the desired level. As a synthesis means, bulk polymerization, suspension polymerization, or emulsion polymerization may be used in addition to solution polymerization.
[0067] The negative photosensitive resin layer N may contain one or more types of alkali-soluble polymers.
[0068] The content of the alkali-soluble polymer is preferably 10% by mass to 90% by mass, more preferably 30% by mass to 70% by mass, and particularly preferably 40% by mass to 60% by mass, relative to the total mass of the negative photosensitive resin layer N. It is preferable to set the content of the alkali-soluble polymer in the negative photosensitive resin layer N to 90% by mass or less from the viewpoint of controlling the development time. On the other hand, it is preferable to set the content of the alkali-soluble polymer in the negative photosensitive resin layer N to 10% by mass or more from the viewpoint of improving edge fuse resistance.
[0069] When the negative photosensitive resin layer N contains two or more kinds of alkali-soluble polymers, it is preferable that the negative photosensitive resin layer N contains two or more kinds of alkali-soluble polymers having a structural unit derived from a monomer having an aromatic hydrocarbon group, or contains an alkali-soluble polymer having a structural unit derived from a monomer having an aromatic hydrocarbon group and an alkali-soluble polymer having no structural unit derived from a monomer having an aromatic hydrocarbon group. In the latter case, the content of the alkali-soluble polymer having a structural unit derived from a monomer having an aromatic hydrocarbon group is preferably 50% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, and particularly preferably 90% by mass or more, based on the total mass of the alkali-soluble polymer.
[0070] -Polymerizable compound- The negative photosensitive resin layer N preferably contains a polymerizable compound. In the present disclosure, the term "polymerizable compound" refers to a compound that has a bond involved in a polymerization reaction or a polymerizable group, and that polymerizes under the action of a polymerization initiator described below. Moreover, the polymerizable compound in the present disclosure is a compound different from the above-mentioned alkali-soluble polymer, and preferably has a molecular weight of less than 5,000. The polymerizable compound is preferably an ethylenically unsaturated compound. From the viewpoints of the strength of the obtained cured film, the substrate adhesion, the suppression of development residues, and the rust prevention properties, it is preferable that the ethylenically unsaturated compound contains an ethylenically unsaturated compound having an acid group, and it is more preferable that the ethylenically unsaturated compound contains a compound represented by formula (M) described later and an ethylenically unsaturated compound having an acid group.
[0071] From the viewpoints of suppressing development residues, rust prevention, and bending resistance of the resulting cured film, the ethylenically unsaturated compound preferably contains a compound represented by the following formula (M) (also simply referred to as "compound M"). Q 2 -R 1 -Q 1 Formula (M) In formula (M), Q1 and Q 2 each independently represents a (meth)acryloyloxy group; R 1 represents a divalent linking group having a chain structure.
[0072] Q in formula (M) 1 and Q 2 From the viewpoint of ease of synthesis, Q 1 and Q 2 are preferably the same group. In addition, Q in formula (M) 1 and Q 2 is preferably an acryloyloxy group from the viewpoint of reactivity. R in formula (M) 1 From the viewpoint of bending resistance of the resulting cured film, 1 -OL 1 -), or a polyalkyleneoxyalkylene group (-(L 1 -O) p -L 1 -), more preferably a hydrocarbon group having 2 to 20 carbon atoms or a polyalkyleneoxyalkylene group, still more preferably an alkylene group having 4 to 20 carbon atoms, and particularly preferably a straight-chain alkylene group having 6 to 18 carbon atoms. The hydrocarbon group may have a chain structure at least in a portion thereof, and the portion other than the chain structure is not particularly limited and may be, for example, a branched, cyclic, or straight-chain alkylene group having 1 to 5 carbon atoms, an arylene group, an ether bond, or a combination thereof. From the viewpoint of bending resistance of the obtained cured film, it is preferable that the alkylene group is an alkylene group or a group combining two or more alkylene groups and one or more arylene groups, more preferably an alkylene group, and particularly preferably a straight-chain alkylene group. In addition, the above L 1 each independently represents an alkylene group, preferably an ethylene group, a propylene group, or a butylene group, and more preferably an ethylene group or a 1,2-propylene group. p represents an integer of 2 or more, and preferably an integer of 2 to 10.
[0073] In addition, Q in compound M 1 and Q 2 The number of atoms in the shortest linking chain between and is preferably 3 to 50, more preferably 4 to 40, even more preferably 6 to 20, and particularly preferably 8 to 12, from the viewpoints of moisture permeability and bending resistance of the resulting cured film. In this disclosure, 1 and Q 2 The number of atoms in the shortest chain connecting Q 1 R to be connected 1 Q from atoms in 2 R to be connected 1 is the shortest number of atoms that can connect to an atom in
[0074] Specific examples of compound M include 1,3-butanediol di(meth)acrylate, tetramethylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,7-heptanediol di(meth)acrylate, 1,8-octanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, 1,4-cyclohexanediol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, hydrogenated bisphenol A di(meth)acrylate, hydrogenated bisphenol F di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, poly(ethylene glycol / propylene glycol) di(meth)acrylate, and polybutylene glycol di(meth)acrylate. The above ester monomers may also be used as mixtures. Among the above compounds, from the viewpoint of bending resistance of the obtained cured film, at least one compound selected from the group consisting of 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, and neopentyl glycol di(meth)acrylate is preferable, at least one compound selected from the group consisting of 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, and 1,10-decanediol di(meth)acrylate is more preferable, and at least one compound selected from the group consisting of 1,9-nonanediol di(meth)acrylate and 1,10-decanediol di(meth)acrylate is particularly preferable.
[0075] The compound M may be used alone or in combination of two or more kinds. From the viewpoints of moisture permeability and bending resistance of the obtained cured film, the content of compound M is preferably 10% by mass to 90% by mass, more preferably 15% by mass to 70% by mass, further preferably 20% by mass to 50% by mass, and particularly preferably 25% by mass to 35% by mass, based on the total mass of the ethylenically unsaturated compounds in the negative photosensitive resin layer N. In the present disclosure, the ethylenically unsaturated compound refers to a compound having an ethylenically unsaturated group and a (weight average) molecular weight of 10,000 or less. Furthermore, from the viewpoints of moisture permeability and bending resistance of the obtained cured film, the content of compound M is preferably 1 mass % to 30 mass %, more preferably 3 mass % to 25 mass %, even more preferably 5 mass % to 20 mass %, and particularly preferably 6 mass % to 14.5 mass %, relative to the total mass of the negative type photosensitive resin layer N.
[0076] The ethylenically unsaturated compound preferably contains a di- or higher functional ethylenically unsaturated compound. In the present disclosure, the term "di- or higher functional ethylenically unsaturated compound" refers to a compound having two or more ethylenically unsaturated groups in one molecule. As the ethylenically unsaturated group in the ethylenically unsaturated compound, a (meth)acryloyl group is preferred. As the ethylenically unsaturated compound, a (meth)acrylate compound is preferred.
[0077] As the ethylenically unsaturated compound, from the viewpoint of the strength of the cured film after curing, it is particularly preferable to include a difunctional ethylenically unsaturated compound (preferably a difunctional (meth)acrylate compound) and a trifunctional or higher ethylenically unsaturated compound (preferably a trifunctional or higher (meth)acrylate compound).
[0078] <<Polymerizable compound B>> The negative photosensitive resin layer N preferably contains a polymerizable compound B. The polymerizable compound B is a compound different from the polymer A. A preferred example of the bond involved in the polymerization reaction in the polymerizable compound B is an ethylenically unsaturated bond.
[0079] The polymerizable group in the polymerizable compound B is not limited as long as it is a group involved in a polymerization reaction. Examples of the polymerizable group in the polymerizable compound B include a group containing an ethylenically unsaturated bond (e.g., a vinyl group, an acryloyl group, a methacryloyl group, a styryl group, and a maleimide group), and a cationic polymerizable group (e.g., an epoxy group and an oxetane group). The polymerizable group is preferably a group containing an ethylenically unsaturated bond (hereinafter, sometimes referred to as an "ethylenically unsaturated group"), and more preferably an acryloyl group or a methacryloyl group.
[0080] The polymerizable compound B is preferably a compound having an ethylenically unsaturated bond, more preferably a compound having one or more ethylenically unsaturated groups in one molecule (i.e., an ethylenically unsaturated compound), and particularly preferably a compound having two or more ethylenically unsaturated groups in one molecule (i.e., a polyfunctional ethylenically unsaturated compound), in terms of superior resolution and peelability. Also, the number of ethylenically unsaturated groups contained in one molecule of the ethylenically unsaturated compound is preferably 6 or less, more preferably 3 or less, and particularly preferably 2 or less, in terms of superior resolution and peelability. In addition, from the viewpoints of curability and the strength and durability of the resulting resin pattern 2 as a permanent film, it is preferable that the polymerizable compound B contains a trifunctional or higher ethylenically unsaturated compound, and it is more preferable that the polymerizable compound B contains a pentafunctional or higher ethylenically unsaturated compound.
[0081] The ethylenically unsaturated compound is preferably a (meth)acrylate compound having one or more (meth)acryloyl groups in one molecule.
[0082] From the viewpoint of achieving a better balance of photosensitivity, resolution, and peelability in the negative photosensitive resin layer N, the polymerizable compound B preferably contains at least one selected from the group consisting of compounds having two ethylenically unsaturated groups in one molecule (i.e., bifunctional ethylenically unsaturated compounds) and compounds having three ethylenically unsaturated groups in one molecule (i.e., trifunctional ethylenically unsaturated compounds), and more preferably contains a compound having two ethylenically unsaturated groups in one molecule.
[0083] Moreover, from the viewpoint of strength and dimensional stability after curing, the polymerizable compound B preferably contains an ethylenically unsaturated compound having an aliphatic cyclic skeleton, more preferably contains a di(meth)acrylate compound having an aliphatic cyclic skeleton, and particularly preferably contains a di(meth)acrylate compound having a dicyclopentanyl structure or a dicyclopentenyl structure. Furthermore, from the viewpoint of strength and dimensional stability after curing, the polymerizable compound B preferably contains an ethylenically unsaturated compound having a dicyclopentanyl structure or a dicyclopentenyl structure.
[0084] In the negative photosensitive resin layer N, the ratio of the content of the bifunctional ethylenically unsaturated compound to the content of the polymerizable compound B is preferably 40% by mass or more, more preferably 60% by mass or more, and particularly preferably more than 70% by mass, from the viewpoint of excellent peelability of the negative photosensitive resin layer N. The upper limit of the content ratio of the bifunctional ethylenically unsaturated compound to the content of the polymerizable compound B is not limited and may be 100% by mass. That is, all of the polymerizable compounds B contained in the negative photosensitive resin layer N may be bifunctional ethylenically unsaturated compounds.
[0085] -Polymerizable compound B1- The negative photosensitive resin layer N according to the present disclosure preferably contains a polymerizable compound B1 having one or more aromatic rings and two ethylenically unsaturated groups in one molecule. The polymerizable compound B1 is a bifunctional ethylenically unsaturated compound having one or more aromatic rings in one molecule among the above-mentioned polymerizable compounds B.
[0086] In the negative photosensitive resin layer, the ratio of the content of the polymerizable compound B1 to the content of the polymerizable compound B is preferably 40% by mass or more, more preferably 50% by mass or more, even more preferably 55% by mass or more, and particularly preferably 60% by mass or more, from the viewpoint of better resolution. The upper limit of the ratio of the content of the polymerizable compound B1 to the content of the polymerizable compound B is not limited. The ratio of the content of the polymerizable compound B1 to the content of the polymerizable compound B is preferably 99% by mass or less, more preferably 95% by mass or less, even more preferably 90% by mass or less, and particularly preferably 85% by mass or less, from the viewpoint of peelability.
[0087] Examples of the aromatic ring in the polymerizable compound B1 include aromatic hydrocarbon rings (e.g., benzene ring, naphthalene ring, and anthracene ring), aromatic heterocycles (e.g., thiophene ring, furan ring, pyrrole ring, imidazole ring, triazole ring, and pyridine ring), and condensed rings thereof. The aromatic ring is preferably an aromatic hydrocarbon ring, and more preferably a benzene ring. The aromatic ring may have a substituent.
[0088] The polymerizable compound B1 preferably has a bisphenol structure, since the resolution is improved by suppressing swelling of the negative photosensitive resin layer N by the developer. Examples of the bisphenol structure include a bisphenol A structure derived from bisphenol A (i.e., 2,2-bis(4-hydroxyphenyl)propane), a bisphenol F structure derived from bisphenol F (i.e., 2,2-bis(4-hydroxyphenyl)methane), and a bisphenol B structure derived from bisphenol B (i.e., 2,2-bis(4-hydroxyphenyl)butane). The bisphenol structure is preferably a bisphenol A structure.
[0089] Examples of the polymerizable compound B1 having a bisphenol structure include compounds having a bisphenol structure and two polymerizable groups (preferably (meth)acryloyl groups) bonded to both ends of the bisphenol structure. Each polymerizable group may be directly bonded to the bisphenol structure. Each polymerizable group may be bonded to the bisphenol structure via one or more alkyleneoxy groups. The alkyleneoxy groups added to both ends of the bisphenol structure are preferably ethyleneoxy groups or propyleneoxy groups, and more preferably ethyleneoxy groups. The number of alkyleneoxy groups added to the bisphenol structure is not limited, but is preferably 4 to 16, and more preferably 6 to 14 per molecule.
[0090] The polymerizable compound B1 having a bisphenol structure is described in JP 2016-224162 A, paragraphs 0072 to 0080. The contents of the above publication are incorporated herein by reference.
[0091] The polymerizable compound B1 is preferably a difunctional ethylenically unsaturated compound having a bisphenol A structure, and more preferably 2,2-bis(4-((meth)acryloxypolyalkoxy)phenyl)propane.
[0092] Examples of 2,2-bis(4-((meth)acryloxypolyalkoxy)phenyl)propane include 2,2-bis(4-(methacryloxydiethoxy)phenyl)propane (FA-324M, Hitachi Chemical Co., Ltd.), 2,2-bis(4-(methacryloxyethoxypropoxy)phenyl)propane, 2,2-bis(4-(methacryloxypentaethoxy)phenyl)propane (BPE-500, Shin-Nakamura Chemical Co., Ltd.), and 2,2-bis(4-(methacryloxydodecaethoxy)phenyl)propane. Examples of suitable ethoxylated (10) bisphenol A diacrylate include 2,2-bis(4-(methacryloxytetrapropoxy)phenyl)propane (FA-3200MY, Hitachi Chemical Co., Ltd.), 2,2-bis(4-(methacryloxypentadecaethoxy)phenyl)propane (BPE-1300, Shin-Nakamura Chemical Co., Ltd.), 2,2-bis(4-(methacryloxydiethoxy)phenyl)propane (BPE-200, Shin-Nakamura Chemical Co., Ltd.), and ethoxylated (10) bisphenol A diacrylate (NK Ester A-BPE-10, Shin-Nakamura Chemical Co., Ltd.).
[0093] The polymerizable compound B1 also includes, for example, a compound represented by the following general formula (I).
[0094] [ka]
[0095] In the general formula (I), R1 and R2 each independently represent a hydrogen atom or a methyl group, A represents C2H4, B represents C3H6, n1 and n3 each independently represent an integer of 1 to 39, n1+n3 represents an integer of 2 to 40, n2 and n4 each independently represent an integer of 0 to 29, n2+n4 represents an integer of 0 to 30, and the arrangement of the repeating units of -(AO)- and -(BO)- may be random or block. In the case of block, either -(AO)- or -(BO)- may be on the bisphenyl group side. n2+n4 is preferably an integer of 0 to 10, more preferably an integer of 0 to 4, further preferably an integer of 0 to 2, and particularly preferably 0. n1+n2+n3+n4 is preferably an integer of 2 to 20, more preferably an integer of 2 to 16, and particularly preferably an integer of 4 to 12.
[0096] The negative photosensitive resin layer N may contain one or more kinds of polymerizable compounds B1.
[0097] The content ratio of the polymerizable compound B1 in the negative photosensitive resin layer N is preferably 10% by mass or more, more preferably 20% by mass or more, based on the total mass of the negative photosensitive resin layer N, from the viewpoint of better resolution. The upper limit of the content ratio of the polymerizable compound B1 is not limited. The content ratio of the polymerizable compound B1 in the negative photosensitive resin layer N is preferably 70% by mass or less, more preferably 60% by mass or less, based on the total mass of the negative photosensitive resin layer N, from the viewpoint of transferability and edge fuse resistance.
[0098] The negative photosensitive resin layer N may contain a polymerizable compound B1 and a polymerizable compound B other than the polymerizable compound B1. Examples of the polymerizable compound B other than the polymerizable compound B1 include a monofunctional ethylenically unsaturated compound (i.e., a compound having one ethylenically unsaturated group in one molecule), a bifunctional ethylenically unsaturated compound having no aromatic ring (i.e., a compound having no aromatic ring and having two ethylenically unsaturated groups in one molecule), and a trifunctional or higher ethylenically unsaturated compound (i.e., a compound having three or more ethylenically unsaturated groups in one molecule).
[0099] Examples of monofunctional ethylenically unsaturated compounds include ethyl (meth)acrylate, ethylhexyl (meth)acrylate, 2-(meth)acryloyloxyethyl succinate, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, and phenoxyethyl (meth)acrylate.
[0100] Examples of difunctional ethylenically unsaturated compounds having no aromatic ring include alkylene glycol di(meth)acrylate, polyalkylene glycol di(meth)acrylate, urethane di(meth)acrylate, and trimethylolpropane diacrylate.
[0101] Examples of alkylene glycol di(meth)acrylates include tricyclodecane dimethanol diacrylate (A-DCP, Shin-Nakamura Chemical Co., Ltd.), tricyclodecane dimethanol dimethacrylate (DCP, Shin-Nakamura Chemical Co., Ltd.), 1,9-nonanediol diacrylate (A-NOD-N, Shin-Nakamura Chemical Co., Ltd.), 1,6-hexanediol diacrylate (A-HD-N, Shin-Nakamura Chemical Co., Ltd.), ethylene glycol dimethacrylate, 1,10-decanediol diacrylate, and neopentyl glycol di(meth)acrylate.
[0102] Examples of polyalkylene glycol di(meth)acrylates include polyethylene glycol di(meth)acrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, and polypropylene glycol di(meth)acrylate.
[0103] Examples of urethane di(meth)acrylate include propylene oxide modified urethane di(meth)acrylate, and ethylene oxide and propylene oxide modified urethane di(meth)acrylate. Commercially available products include 8UX-015A (Taisei Fine Chemical Co., Ltd.), UA-32P (Shin-Nakamura Chemical Co., Ltd.), and UA-1100H (Shin-Nakamura Chemical Co., Ltd.).
[0104] Examples of trifunctional or higher ethylenically unsaturated compounds include dipentaerythritol (tri / tetra / penta / hexa)(meth)acrylate, pentaerythritol (tri / tetra)(meth)acrylate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, trimethylolethane tri(meth)acrylate, isocyanuric acid tri(meth)acrylate, glycerin tri(meth)acrylate, and alkylene oxide modified products thereof. In the present disclosure, "(tri / tetra / penta / hexa)(meth)acrylate" is a concept that includes tri(meth)acrylate, tetra(meth)acrylate, penta(meth)acrylate, and hexa(meth)acrylate. In the present disclosure, "(tri / tetra)(meth)acrylate" is a concept that includes tri(meth)acrylate and tetra(meth)acrylate.
[0105] Examples of alkylene oxide modified trifunctional or higher ethylenically unsaturated compounds include caprolactone modified (meth)acrylate compounds (e.g., KAYARAD (registered trademark) DPCA-20 manufactured by Nippon Kayaku Co., Ltd., and A-9300-1CL manufactured by Shin-Nakamura Chemical Co., Ltd.), alkylene oxide modified (meth)acrylate compounds (e.g., KAYARAD RP-1040 manufactured by Nippon Kayaku Co., Ltd., ATM-35E manufactured by Shin-Nakamura Chemical Co., Ltd., A-9300 manufactured by Shin-Nakamura Chemical Co., Ltd., and EBECRYL (registered trademark) manufactured by Daicel-Allnex Corporation). 135), ethoxylated glycerin triacrylate (e.g., A-GLY-9E manufactured by Shin-Nakamura Chemical Co., Ltd.), ARONIX (registered trademark) TO-2349 (Toagosei Co., Ltd.), ARONIX M-520 (Toagosei Co., Ltd.), and ARONIX M-510 (Toagosei Co., Ltd.).
[0106] Examples of the polymerizable compound B other than the polymerizable compound B1 include the polymerizable compounds having an acid group described in paragraphs 0025 to 0030 of JP-A No. 2004-239942.
[0107] In one embodiment, the negative photosensitive resin layer N preferably contains a polymerizable compound B1 and a trifunctional or higher ethylenically unsaturated compound, and more preferably contains a polymerizable compound B1 and two or more trifunctional or higher ethylenically unsaturated compounds. In the above embodiment, the mass ratio of the polymerizable compound B1 to the trifunctional or higher ethylenically unsaturated compounds ([total mass of the polymerizable compound B1]:[total mass of the trifunctional or higher ethylenically unsaturated compounds] is preferably 1:1 to 5:1, more preferably 1.2:1 to 4:1, and particularly preferably 1.5:1 to 3:1.
[0108] The weight average molecular weight (Mw) of the polymerizable compound B is preferably from 200 to 3,000, more preferably from 280 to 2,200, and particularly preferably from 300 to 2,200.
[0109] The negative photosensitive resin layer N may contain one or more kinds of polymerizable compounds B.
[0110] The content ratio of the polymerizable compound B in the negative photosensitive resin layer N is preferably 10% by mass to 70% by mass, more preferably 20% by mass to 60% by mass, and particularly preferably 20% by mass to 50% by mass, relative to the total mass of the negative photosensitive resin layer N.
[0111] -Multifunctional epoxy resin- From the viewpoint of the strength and durability of the resulting pattern 2 as a permanent film, the negative photosensitive resin layer N preferably contains a polyfunctional epoxy resin, and more preferably contains a polyfunctional epoxy resin, a hydroxy group-containing compound, and a photocationic polymerization initiator. Examples of polyfunctional epoxy resins include epoxy compounds having at least two oxirane groups in one molecule, and epoxy compounds containing at least two epoxy groups having an alkyl group at the β-position in one molecule.
[0112] Examples of the epoxy compound having at least two oxirane groups in one molecule include bisphenol F type epoxy resin (Epotohto YDF-170, manufactured by Tohto Kasei Co., Ltd.), bixylenol type or biphenol type epoxy resin (YX4000, manufactured by Japan Epoxy Resins Co., Ltd., etc.) or a mixture thereof, heterocyclic epoxy resins having an isocyanurate skeleton or the like (TEPIC, manufactured by Nissan Chemical Industries, Ltd., Araldite PT810, manufactured by Huntsman Advanced Materials, etc.), bisphenol A type epoxy resin, novolac type epoxy resin, bisphenol F type epoxy resin, hydrogenated bisphenol A type epoxy resin, bisphenol S type epoxy resin, phenol novolac type epoxy resin, cresol novolac type epoxy resin, halogenated epoxy resin (e.g. low brominated epoxy resin, high halogenated epoxy resin, brominated phenol novolac type epoxy resin, etc.), allyl group-containing bisphenol A type epoxy resin, bisphenol S type epoxy resin, phenol novolac type epoxy resin, cresol novolac type epoxy resin, halogenated epoxy resin (e.g. low brominated epoxy resin, high halogenated epoxy resin, brominated phenol novolac type epoxy resin, etc.), and mixtures thereof. Phenol A type epoxy resin, trisphenolmethane type epoxy resin, diphenyldimethanol type epoxy resin, phenolbiphenylene type epoxy resin, dicyclopentadiene type epoxy resin (HP-7200, HP-7200H; DIC Corporation, etc.), glycidylamine type epoxy resin (diaminodiphenylmethane type epoxy resin, diglycidylaniline, triglycidylaminophenol, etc.), glycidyl ester type epoxy resin (phthalic acid diglycidyl ester, adipic acid diglycidyl ester, hexahydrophthalic acid diglycidyl ester, dimer acid diglycidyl ester, etc.), hydantoin type epoxy resin, alicyclic epoxy resin (3,4-epoxycyclohexylmethyl-3',4'-epoxycyclohexanecarboxylate, bis(3,4-epoxycyclohexylmethyl)adipate, dicyclopentadiene diepoxide, GT-300, GT-400, ZEHPE3150;(manufactured by Daicel Corporation), imide-type alicyclic epoxy resins, trihydroxyphenylmethane-type epoxy resins, bisphenol A novolac-type epoxy resins, tetraphenylolethane-type epoxy resins, glycidyl phthalate resins, tetraglycidylxylenoylethane resins, naphthalene-group-containing epoxy resins (naphthol aralkyl-type epoxy resins, naphthol novolac-type epoxy resins, tetrafunctional naphthalene-type epoxy resins; commercially available products include ESN-190, ESN-360; manufactured by Nippon Steel Chemical Co., Ltd.), "HP-4032, EXA-4750, EXA-4700; manufactured by DIC Corporation," etc.), polyphenol compounds obtained by addition reaction of phenol compounds with diolefin compounds such as divinylbenzene and dicyclopentadiene, and reaction products of epichlorohydrin, ring-opening polymerization products of 4-vinylcyclohexene-1-oxide epoxidized with peracetic acid, etc., bisphenol A type epoxy resins, octafunctional bisphenol A novolac type epoxy resins (e.g., manufactured by Resolution Performance Products, EPON SU-8), epoxy resins obtained by reacting the alcoholic hydroxyl group of a bisphenol F type epoxy resin with epichlorohydrin (e.g., NER-7604 manufactured by Nippon Kayaku Co., Ltd.), epoxy resins obtained by reacting the alcoholic hydroxyl group of a bisphenol A type epoxy resin with epichlorohydrin (e.g., NER-1302 manufactured by Nippon Kayaku Co., Ltd.), o-cresol novolac type epoxy resins (e.g., EOCN4400 manufactured by Nippon Kayaku Co., Ltd.), biphenylphenol novolac type epoxy resins obtained by reacting the phenolic hydroxyl group of a resin obtained by reacting di(methoxymethylphenyl) with phenol with epichlorohydrin (e.g., EOCN4400 manufactured by Nippon Kayaku Co., Ltd.), NC-3000H), epoxy resins with cyclic phosphorus-containing structures, α-methylstilbene type liquid crystal epoxy resins, dibenzoyloxybenzene type liquid crystal epoxy resins, azophenyl type liquid crystal epoxy resins, azomethine phenyl type liquid crystal epoxy resins, binaphthyl type liquid crystal epoxy resins, azine type epoxy resins, glycidyl methacrylate copolymer epoxy resins (CP-50S, CP-50M;Examples of epoxy resins that can be used include epoxy resins manufactured by Nippon Oil & Fats Co., Ltd. (e.g.), copolymer epoxy resins of cyclohexylmaleimide and glycidyl methacrylate, bis(glycidyloxyphenyl)fluorene type epoxy resins, and bis(glycidyloxyphenyl)adamantane type epoxy resins. These may be used alone or in combination of two or more.
[0113] In addition to the above-mentioned epoxy compounds having at least two oxirane groups per molecule, epoxy compounds containing at least two epoxy groups having an alkyl group at the β-position per molecule can be used, and compounds containing an epoxy group substituted with an alkyl group at the β-position (more specifically, a β-alkyl-substituted glycidyl group, etc.) are particularly preferred. The epoxy compound containing at least an epoxy group having an alkyl group at the β-position may have two or more epoxy groups in one molecule all of which are β-alkyl-substituted glycidyl groups, or at least one epoxy group may be a β-alkyl-substituted glycidyl group.
[0114] The oxetane compound may, for example, be an oxetane compound having at least two oxetanyl groups in one molecule. Specifically, for example, bis[(3-methyl-3-oxetanylmethoxy)methyl]ether, bis[(3-ethyl-3-oxetanylmethoxy)methyl]ether, 1,4-bis[(3-methyl-3-oxetanylmethoxy)methyl]benzene, 1,4-bis[(3-ethyl-3-oxetanylmethoxy)methyl]benzene, (3-methyl-3-oxetanyl)methyl acrylate, (3-ethyl-3-oxetanyl)methyl acrylate, (3-methyl-3-oxetanyl)methyl methacrylate, ( Examples of the oxetanes include polyfunctional oxetanes such as 3-ethyl-3-oxetanyl)methyl methacrylate or oligomers or copolymers thereof, as well as ether compounds of compounds having an oxetane group and resins having a hydroxyl group such as novolak resins, poly(p-hydroxystyrene), cardo-type bisphenols, calixarenes, calixresorcinarenes, and silsesquioxane. Examples of the ether compounds include copolymers of unsaturated monomers having an oxetane ring and alkyl (meth)acrylates.
[0115] As the epoxy resin, any epoxy resin can be used as long as it has two or more epoxy groups in one molecule, but the epoxy equivalent of the epoxy resin is preferably 100 g / equivalent to 500 g / equivalent, more preferably 100 g / equivalent to 300 g / equivalent, so that a sufficient curing speed can be obtained. The epoxy equivalent here means a value measured by a method conforming to JIS K-7236. As the type of epoxy resin, a glycidyl ether type, a glycidyl ester type, a glycidyl amine type, an alicyclic type, etc. can be used. Since the liquid storage stability is good, the glycidyl ether type and the glycidyl ester type are preferred, and the glycidyl ether type is most preferred. From the viewpoint of developability, the epoxy resin is preferably liquid at room temperature (25° C.) and has a viscosity of preferably 5,000 mPa s or less, and more preferably 1,000 mPa s or less at 25° C. These epoxy resins can be used alone or in combination of two or more kinds. Specific examples of such epoxy resins include glycidyl ether type resins such as sorbitol polyglycidyl ether, polyglycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, diglycerol polyglycidyl ether, glycerol polyglycidyl ether, trimethylolpropane polyglycidyl ether, resorcinol diglycidyl ether, neopentyl glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, and polypropylene glycol diglycidyl ether, and also glycidyl ester type resins such as phthalic acid diglycidyl ester, tetrahydrophthalic acid diglycidyl ester, and hexahydrophthalic acid diglycidyl ester.
[0116] The negative photosensitive resin layer N may contain one type of polyfunctional epoxy resin alone or two or more types of polyfunctional epoxy resins. The content of the polyfunctional epoxy resin in the negative photosensitive resin layer N is preferably 10% by mass to 90% by mass, and more preferably 20% by mass to 70% by mass, based on the total mass of the negative photosensitive resin layer N.
[0117] -Hydroxy group-containing compounds- From the viewpoint of the strength and durability of the resulting pattern 2 as a permanent film, the negative photosensitive resin layer N preferably contains a hydroxy group-containing compound. As the hydroxy group-containing compound, a polyol compound or a phenol-based compound can be appropriately used. The polyol compound contains a hydroxyl group that reacts with the epoxy group in the epoxy resin under the influence of an acid catalyst, and acts as a reactive diluent. In particular, it is preferable to contain polycaprolactone polyol. By containing polycaprolactone polyol, the dried coating film obtained by drying the solvent as necessary after applying the resin composition is softened, so that stress induction during the production of the laminate is avoided, shrinkage is reduced, and cracks in the resin pattern 2, which is a permanent film, can be prevented.
[0118] As the polyol compound, commercially available polyester polyols can be used. Specific examples include "Placcel 205" with a molecular weight of 530 and an OH value (also called "hydroxyl value") of 210 mgKOH / g, "Placcel 210" with a molecular weight of 1,000 and an OH value of 110 mgKOH / g, "Placcel 220" with a molecular weight of 2,000 and an OH value of 56 mgKOH / g (all trade names, manufactured by Daicel Corporation), "Capa 2054" with a molecular weight of 550 and an OH value of 204 mgKOH / g, "Capa 2100" with a molecular weight of 1,000 and an OH value of 112 mgKOH / g, and "Capa 2200" with a molecular weight of 2,000 and an OH value of 56 mgKOH / g (all trade names, manufactured by Perstorp). Examples of the phenol-based compound include phenol novolac resin, cresol novolac resin, polyfunctional bisphenol A novolac resin, biphenylphenol novolac resin, phenol resin having a trishydroxyphenylmethane skeleton, phenol resin having a terpene diphenol skeleton, and phenol resins made from various phenols such as bisphenol A and bisphenol F. The hydroxyl value of the hydroxyl group-containing compound is preferably 90 mgKOH / g to 300 mgKOH / g, more preferably 100 mgKOH / g to 250 mgKOH / g. The hydroxyl group-containing compound may be used alone or in combination of two or more kinds.
[0119] The negative photosensitive resin layer N may contain one kind of hydroxy group-containing compound alone or two or more kinds of hydroxy group-containing compounds. The content of the hydroxy group-containing compound in the negative photosensitive resin layer N is preferably 1% by mass to 35% by mass, and more preferably 5% by mass to 25% by mass, based on the total mass of the negative photosensitive resin layer N.
[0120] -Photopolymerization initiator- The negative photosensitive resin layer N preferably contains a photopolymerization initiator. The photopolymerization initiator is a compound that initiates polymerization of a polymerizable compound (e.g., polymerizable compound B) upon receiving actinic rays (e.g., ultraviolet rays, visible rays, and X-rays). Also,
[0121] The photopolymerization initiator is not limited, and a known photopolymerization initiator can be used. Examples of the photopolymerization initiator include a photoradical polymerization initiator and a photocationic polymerization initiator, and from the viewpoint of curability, a photoradical polymerization initiator is preferred. From the viewpoint of the strength and durability of the resulting resin pattern 2 as a permanent film, the negative photosensitive resin layer N preferably contains a photocationic polymerization initiator.
[0122] Examples of the photoradical polymerization initiator include a photopolymerization initiator having an oxime ester structure, a photopolymerization initiator having an α-aminoalkylphenone structure, a photopolymerization initiator having an α-hydroxyalkylphenone structure, a photopolymerization initiator having an acylphosphine oxide structure, and a photopolymerization initiator having an N-phenylglycine structure.
[0123] From the viewpoints of photosensitivity, visibility of exposed areas, visibility of non-exposed areas, and resolution, the negative photosensitive resin layer N preferably contains at least one photoradical polymerization initiator selected from the group consisting of 2,4,5-triarylimidazole dimers and derivatives of 2,4,5-triarylimidazole dimers. Note that the two 2,4,5-triarylimidazole structures in the 2,4,5-triarylimidazole dimer and its derivatives may be the same or different.
[0124] Examples of derivatives of 2,4,5-triarylimidazole dimers include 2-(o-chlorophenyl)-4,5-diphenylimidazole dimer, 2-(o-chlorophenyl)-4,5-di(methoxyphenyl)imidazole dimer, 2-(o-fluorophenyl)-4,5-diphenylimidazole dimer, 2-(o-methoxyphenyl)-4,5-diphenylimidazole dimer, and 2-(p-methoxyphenyl)-4,5-diphenylimidazole dimer.
[0125] Examples of the photoradical polymerization initiator include the polymerization initiators described in paragraphs 0031 to 0042 of JP-A No. 2011-95716 and paragraphs 0064 to 0081 of JP-A No. 2015-14783.
[0126] Examples of photoradical polymerization initiators include ethyl dimethylaminobenzoate (DBE, CAS No. 10287-53-3), benzoin methyl ether, anisyl (p,p'-dimethoxybenzyl), and benzophenone.
[0127] Commercially available photoradical polymerization initiators include, for example, TAZ-110 (Midori Chemical Co., Ltd.), TAZ-111 (Midori Chemical Co., Ltd.), 1-[4-(phenylthio)]phenyl-1,2-octanedione-2-(O-benzoyloxime) (trade name: IRGACURE (registered trademark) OXE-01, BASF), 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone-1-(O-acetyloxime) (trade name: IRGACURE OXE-02, BASF), IRGACURE OXE-03 (BASF), IRGACURE OXE-04 (BASF), 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone (trade name: Omnirad 379EG, IGM Resins), BV), 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one (trade name: Omnirad 907, IGM Resins BV), 2-hydroxy-1-{4-[4-(2-hydroxy-2-methylpropionyl)benzyl]phenyl}-2-methylpropan-1-one (trade name: Omnirad 127, IGM Resins BV), 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone-1 (trade name: Omnirad 369, IGM Resins BV), 2-hydroxy-2-methyl-1-phenylpropan-1-one (trade name: Omnirad 1173, IGM Resins BV), 1-hydroxycyclohexyl phenyl ketone (trade name: Omnirad 184, IGM Resins BV), 2,2-dimethoxy-1,2-diphenylethan-1-one (trade name: Omnirad 651, IGM Resins BV), 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (trade name: Omnirad TPO H, IGM Resins BV), bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (trade name: Omnirad 819, IGM Resins BVExamples of photoinitiators include oxime ester-based photoinitiators (trade name: Lunar 6, DKSH Japan Co., Ltd.), 2,2'-bis(2-chlorophenyl)-4,4',5,5'-tetraphenyl-1,2'-biimidazole (also known as 2-(2-chlorophenyl)-4,5-diphenylimidazole dimer, trade name: B-CIM, Hampford Co., Ltd.), and 2-(o-chlorophenyl)-4,5-diphenylimidazole dimer (trade name: BCTB, Tokyo Chemical Industry Co., Ltd.).
[0128] Among them, the photoradical polymerization initiator preferably contains at least one selected from the group consisting of 2,4,5-triarylimidazole dimer and derivatives of 2,4,5-triarylimidazole dimer.
[0129] A photocationic polymerization initiator (i.e., a photoacid generator) is a compound that generates cations when irradiated with radiation such as ultraviolet light, far ultraviolet light, excimer lasers such as KrF and ArF, X-rays, or electron beams, and the cations can serve as polymerization initiators. The photocationic polymerization initiator is preferably a compound that responds to active light having a wavelength of 300 nm or more, preferably 300 to 450 nm, and generates an acid. However, the chemical structure of the photocationic polymerization initiator is not limited. In addition, even if the photocationic polymerization initiator is not directly sensitive to active light having a wavelength of 300 nm or more, it can be preferably used in combination with a sensitizer as long as it is a compound that responds to active light having a wavelength of 300 nm or more and generates an acid by using the sensitizer in combination.
[0130] Examples of the photocationic polymerization initiator include aromatic iodonium complex salts and aromatic sulfonium complex salts. Specific examples of aromatic iodonium complex salts include diphenyliodonium tetrakis(pentafluorophenyl)borate, diphenyliodonium hexafluorophosphate, diphenyliodonium hexafluoroantimonate, di(4-nonylphenyl)iodonium hexafluorophosphate, triylcumyliodonium tetrakis(pentafluorophenyl)borate (manufactured by Rhodia, trade name: Rhodosil PI2074), and di(4-tert-butyl)iodonium tris(trifluoromethanesulfonyl)methanide (manufactured by BASF, trade name: CGI BBI-C1). Specific examples of aromatic sulfonium complex salts include 4-thiophenyldiphenylsulfonium hexafluoroantimonate (manufactured by San-Apro, trade name CPI-101A), thiophenyldiphenylsulfonium tris(pentafluoroethyl)trifluorophosphate (manufactured by San-Apro, trade name CPI-210S), 4-{4-(2-chlorobenzoyl)phenylthio}phenylbis(4-fluorophenyl)sulfonium hexafluoroantimonate (manufactured by ADEKA, trade name SP-172), a mixture of aromatic sulfonium hexafluoroantimonates containing 4-thiophenyldiphenylsulfonium hexafluoroantimonate (manufactured by ACETO Corporate USA, trade name CPI-6976), and triphenylsulfonium tris(trifluoromethanesulfonyl)methanide (manufactured by BASF, trade name CGI TPS-C1), tris[4-(4-acetylphenyl)sulfonylphenyl]sulfonium tris(trifluoromethylsulfonyl)methide (BASF, trade name GSID 26-1), tris[4-(4-acetylphenyl)sulfonylphenyl]sulfonium tetrakis(2,3,4,5,6-pentafluorophenyl)borate (BASF, trade name Irgacure PAG290), etc. are preferably used.
[0131] Of the above photocationic polymerization initiators, from the viewpoints of vertical rectangular processability and thermal stability, aromatic sulfonium complex salts are preferred, and 4-{4-(2-chlorobenzoyl)phenylthio}phenylbis(4-fluorophenyl)sulfonium hexafluoroantimonate, a mixture of aromatic sulfonium hexafluoroantimonates containing 4-thiophenyldiphenylsulfonium hexafluoroantimonate, or tris[4-(4-acetylphenyl)sulfonylphenyl]sulfonium tetrakis(2,3,4,5,6-pentafluorophenyl)borate is particularly preferred.
[0132] The photocationic polymerization initiator is preferably a photocationic polymerization initiator that generates an acid having a pKa of 4 or less, more preferably a photocationic polymerization initiator that generates an acid having a pKa of 3 or less, and particularly preferably a photocationic polymerization initiator that generates an acid having a pKa of 2 or less. There is no lower limit for the pKa. The pKa of the acid generated from the photocationic polymerization initiator is preferably, for example, -10.0 or more.
[0133] The photocationic polymerization initiator includes an ionic photocationic polymerization initiator and a nonionic photocationic polymerization initiator.
[0134] Examples of the ionic photocationic polymerization initiator include onium salt compounds (eg, diaryliodonium salt compounds and triarylsulfonium salt compounds) and quaternary ammonium salt compounds.
[0135] Examples of the ionic photocationic polymerization initiator include the ionic photocationic polymerization initiators described in paragraphs 0114 to 0133 of JP-A No. 2014-85643.
[0136] Examples of nonionic photocationic polymerization initiators include trichloromethyl-s-triazine compounds, diazomethane compounds, imide sulfonate compounds, and oxime sulfonate compounds. Examples of trichloromethyl-s-triazine compounds, diazomethane compounds, and imide sulfonate compounds include compounds described in paragraphs 0083 to 0088 of JP 2011-221494 A. Examples of oxime sulfonate compounds include compounds described in paragraphs 0084 to 0088 of WO 2018 / 179640 A.
[0137] The negative photosensitive resin layer N may contain one or more types of photopolymerization initiators.
[0138] The content of the photopolymerization initiator in the negative photosensitive resin layer N is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and particularly preferably 1.0% by mass or more, based on the total mass of the negative photosensitive resin layer N. There is no upper limit to the content of the photopolymerization initiator. The content of the photopolymerization initiator is preferably 10% by mass or less, more preferably 5% by mass or less, based on the total mass of the negative photosensitive resin layer N.
[0139] -Metal oxidation inhibitor- The negative photosensitive resin layer N preferably contains a metal oxidation inhibitor. The metal oxidation inhibitor is preferably a compound having an aromatic ring containing a nitrogen atom in the molecule. In addition, for the metal oxidation inhibitor, the aromatic ring containing a nitrogen atom is preferably at least one ring selected from the group consisting of an imidazole ring, a triazole ring, a tetrazole ring, a thiadiazole ring, and condensed rings of any of these with other aromatic rings, and the aromatic ring containing a nitrogen atom is more preferably an imidazole ring or a condensed ring of an imidazole ring with other aromatic ring. The other aromatic ring may be a homocyclic ring or a heterocyclic ring, but is preferably a homocyclic ring, more preferably a benzene ring or a naphthalene ring, and even more preferably a benzene ring. Preferred examples of the metal oxidation inhibitor include imidazole, benzimidazole, tetrazole, mercaptothiadiazole, and benzotriazole, and imidazole, benzimidazole, and benzotriazole are more preferred. Commercially available products may be used as the metal oxidation inhibitor, and for example, BT120, which contains benzotriazole, manufactured by Johoku Chemical Industry Co., Ltd., can be preferably used.
[0140] Preferred examples of the metal oxidation inhibitor include a benzotriazole compound or a carboxybenzotriazole compound. Examples of benzotriazole compounds include 1,2,3-benzotriazole, 1-chloro-1,2,3-benzotriazole, bis(N-2-ethylhexyl)aminomethylene-1,2,3-benzotriazole, bis(N-2-ethylhexyl)aminomethylene-1,2,3-tolyltriazole, and bis(N-2-hydroxyethyl)aminomethylene-1,2,3-benzotriazole. Examples of the carboxybenzotriazole compound include 4-carboxy-1,2,3-benzotriazole, 5-carboxy-1,2,3-benzotriazole, N-(N,N-di-2-ethylhexyl)aminomethylenecarboxybenzotriazole, N-(N,N-di-2-hydroxyethyl)aminomethylenecarboxybenzotriazole, and N-(N,N-di-2-ethylhexyl)aminoethylenecarboxybenzotriazole. Examples of commercially available products of the carboxybenzotriazole compound include CBT-1 (Johoku Chemical Industry Co., Ltd.).
[0141] The negative photosensitive resin layer N may contain one or more kinds of metal oxidation inhibitors. The content of the metal oxidation inhibitor is preferably 0.1% by mass to 20% by mass, more preferably 0.5% by mass to 10% by mass, and even more preferably 1% by mass to 5% by mass, relative to the total mass of the negative photosensitive resin layer N.
[0142] -Optional ingredients- The negative photosensitive resin layer N may contain components other than the above-mentioned components (hereinafter, sometimes referred to as "optional components"). Examples of the optional components include dyes, surfactants, and additives other than the above-mentioned components.
[0143] <<Dye>> From the viewpoints of visibility of exposed areas, visibility of unexposed areas, pattern visibility after development, and resolution, the negative photosensitive resin layer N preferably contains a dye (hereinafter sometimes referred to as "dye NC") whose maximum absorption wavelength in the color-developing wavelength range of 400 nm to 780 nm is 450 nm or more and whose maximum absorption wavelength changes depending on an acid, a base, or a radical. Although the detailed mechanism is unclear, when the negative photosensitive resin layer N contains the dye NC, the adhesion with the layer adjacent to the negative photosensitive resin layer N is improved, and the resolution is more excellent.
[0144] In the present disclosure, the term "the maximum absorption wavelength is changed by an acid, a base, or a radical" used in relation to a dye may mean any of an embodiment in which a dye in a colored state is decolorized by an acid, a base, or a radical, an embodiment in which a dye in a decolorized state develops color by an acid, a base, or a radical, and an embodiment in which a dye in a colored state changes to a colored state of another hue.
[0145] Specifically, the dye NC may be a compound that changes from a decolorized state to develop a color upon exposure, or may be a compound that changes from a colored state to develop a color upon exposure. In the above embodiment, the dye NC may be a dye whose color-developing or decolorizing state changes due to the action of an acid, base, or radical generated upon exposure. The dye NC may also be a dye whose color-developing or decolorizing state changes as a result of a change in the state (e.g., pH) within the negative photosensitive resin layer N due to an acid, base, or radical generated upon exposure. On the other hand, the dye NC may be a dye whose color-developing or decolorizing state changes upon direct stimulation by an acid, base, or radical without exposure.
[0146] From the viewpoints of visibility of exposed areas, visibility of unexposed areas, and resolution, dye NC is preferably a dye whose maximum absorption wavelength changes in response to an acid or a radical, and more preferably a dye whose maximum absorption wavelength changes in response to a radical.
[0147] From the viewpoints of visibility of exposed areas, visibility of unexposed areas, and resolution, it is preferable that the negative photosensitive resin layer N contains, as the dye NC, both a dye whose maximum absorption wavelength changes due to radicals, and a photoradical polymerization initiator.
[0148] From the viewpoint of visibility of exposed areas and visibility of non-exposed areas, the dye NC is preferably a dye that develops color in response to an acid, a base, or a radical.
[0149] An example of the color-developing mechanism of the dye NC is a mode in which a negative-type photosensitive resin layer N containing a photoradical polymerization initiator, a photocationic polymerization initiator (i.e., a photoacid generator), or a photobase generator is exposed to light, and a radical-reactive dye, an acid-reactive dye, or a base-reactive dye (e.g., a leuco dye) develops color due to a radical, acid, or base generated from the photoradical polymerization initiator, the photocationic polymerization initiator, or the photobase generator.
[0150] In dye NC, the maximum absorption wavelength in the wavelength range of 400 nm to 780 nm during color development is preferably 550 nm or more, more preferably 550 nm to 700 nm, and particularly preferably 550 to 650 nm, from the viewpoints of visibility of exposed areas and visibility of non-exposed areas.
[0151] Furthermore, the dye NC may have one or more maximum absorption wavelengths in the wavelength range of 400 nm to 780 nm during color development. When the dye NC has two or more maximum absorption wavelengths in the wavelength range of 400 nm to 780 nm during color development, the maximum absorption wavelength having the highest absorbance among the two or more maximum absorption wavelengths may be 450 nm or more.
[0152] The maximum absorption wavelength of the dye NC is measured by measuring the transmission spectrum of a solution containing the dye NC (liquid temperature: 25°C) in the range of 400 nm to 780 nm using a spectrophotometer (UV3100, Shimadzu Corporation) in an atmospheric environment and detecting the wavelength at which the light intensity is minimum (maximum absorption wavelength).
[0153] Examples of the dye that develops or loses color upon exposure include leuco compounds. Examples of the dye that loses color upon exposure include leuco compounds, diarylmethane dyes, oxazine dyes, xanthene dyes, iminonaphthoquinone dyes, azomethine dyes, and anthraquinone dyes. From the viewpoint of visibility of the exposed portion and the non-exposed portion, it is preferable that the dye NC is a leuco compound.
[0154] Examples of the leuco compound include a leuco compound having a triarylmethane skeleton (triarylmethane dye), a leuco compound having a spiropyran skeleton (spiropyran dye), a leuco compound having a fluoran skeleton (fluoran dye), a leuco compound having a diarylmethane skeleton (diarylmethane dye), a leuco compound having a rhodamine lactam skeleton (rhodamine lactam dye), a leuco compound having an indolylphthalide skeleton (indolylphthalide dye), and a leucoauramine skeleton (leucoauramine dye). The leuco compound is preferably a triarylmethane dye or a fluoran dye, and more preferably a leuco compound having a triphenylmethane skeleton (triphenylmethane dye) or a fluoran dye.
[0155] From the viewpoint of visibility of the exposed portion and visibility of the non-exposed portion, the leuco compound preferably has a lactone ring, a sultine ring, or a sultone ring. The lactone ring, the sultine ring, or the sultone ring contained in the leuco compound can be reacted with a radical generated from a photoradical polymerization initiator or an acid generated from a photocationic polymerization initiator to change the leuco compound to a ring-closed state to cause discoloration, or to change the leuco compound to a ring-open state to cause color development. The leuco compound is preferably a compound having a lactone ring, a sultine ring, or a sultone ring, and the lactone ring, the sultine ring, or the sultone ring is opened by a radical or an acid to cause color development, and more preferably a compound having a lactone ring, and the lactone ring is opened by a radical or an acid to cause color development.
[0156] Specific examples of leuco compounds include p,p',p"-hexamethyltriaminotriphenylmethane (leuco crystal violet), Pergascript Blue SRB (Ciba-Geigy), crystal violet lactone, malachite green lactone, benzoyl leuco methylene blue, 2-(N-phenyl-N-methylamino)-6-(Np-tolyl-N-ethyl)aminofluoran, 2-anilino-3-methyl-6-(N-ethyl-p-toluidino)fluoran, 3,6-dimethoxyfluoran, 3-(N,N-diethylamino)-5-methyl-7-(N,N-dibenzylamino)fluoran, 3-(N-cyclohexyl-N-methylamino)-6-(N-phenyl-N-methyl ... -methyl-7-anilinofluoran, 3-(N,N-diethylamino)-6-methyl-7-anilinofluoran, 3-(N,N-diethylamino)-6-methyl-7-xylidinofluoran, 3-(N,N-diethylamino)-6-methyl-7-chlorofluoran, 3-(N,N-diethylamino)-6-methoxy-7-aminofluoran, 3-(N,N-diethylamino)-7-(4-chloroanilino)fluoran, 3-(N,N-diethylamino)-7-chlorofluoran, 3-(N,N-diethylamino)- 3-(N,N-diethylamino)-7-benzylaminofluoran, 3-(N,N-diethylamino)-7,8-benzofluoran, 3-(N,N-dibutylamino)-6-methyl-7-anilinofluoran, 3-(N,N-dibutylamino)-6-methyl-7-xylidinofluoran, 3-piperidino-6-methyl-7-anilinofluoran, 3-pyrrolidino-6-methyl-7-anilinofluoran, 3,3-bis(1-ethyl-2-methylindol-3-yl)phthalide, 3,3-bis(1-n-butyl-2-methylindol-3-yl)phthalide 3-(4-diethylamino-2-ethoxyphenyl)-3-(1-ethyl-2-methylindol-3-yl)phthalide, 3,3-bis(p-dimethylaminophenyl)-6-dimethylaminophthalide, 3-(4-diethylamino-2-ethoxyphenyl)-3-(1-ethyl-2-methylindol-3-yl)-4-azaphthalide, 3-(4-diethylaminophenyl)-3-(1-ethyl-2-methylindol-3-yl)phthalide, and 3',6'-bis(diphenylamino)spiroisobenzofuran-1(3H),9'-[9H]xanthen-3-one.
[0157] Examples of the pigment NC include dyes. Specific examples of dyes include brilliant green, ethyl violet, methyl green, crystal violet, basic fuchsin, methyl violet 2B, quinaldine red, rose bengal, metanil yellow, thymolsulfophthalein, xylenol blue, methyl orange, paramethyl red, Congo red, benzopurpurin 4B, α-naphthyl red, Nile blue 2B, Nile blue A, methyl violet, malachite green, parafuchsin, Victoria Pure Blue-naphthalenesulfonate, Victoria Pure Blue BOH (Hodogaya Chemical Co., Ltd.), oil blue #603 (Orient Chemical Co., Ltd.), oil pink #312 (Orient Chemical Co., Ltd.), oil red 5B (Orient Chemical Co., Ltd.), oil scarlet #308 (Orient Chemical Co., Ltd.), and the like. Examples of the pigments that can be used include rhodamine B, rhodamine 6G, sulforhodamine B, auramine, 4-p-diethylaminophenyliminonaphthoquinone, 2-carboxyanilino-4-p-diethylaminophenyliminonaphthoquinone, 2-carboxystearylamino-4-pN,N-bis(hydroxyethyl)amino-phenyliminonaphthoquinone, 1-phenyl-3-methyl-4-p-diethylaminophenylimino-5-pyrazolone, and 1-β-naphthyl-4-p-diethylaminophenylimino-5-pyrazolone.
[0158] From the viewpoints of visibility of exposed areas, visibility of unexposed areas, pattern visibility after development, and resolution, dye NC is preferably a dye whose maximum absorption wavelength changes in response to radicals, and more preferably a dye that develops color in response to radicals.
[0159] Preferably, dye NC is leuco crystal violet, crystal violet lactone, brilliant green, or Victoria Pure Blue-naphthalenesulfonate.
[0160] The negative photosensitive resin layer N may contain one type of dye alone or two or more types of dyes.
[0161] From the viewpoints of visibility of exposed areas, visibility of unexposed areas, and pattern visibility and resolution after development, the content of the dye is preferably 0.1 mass % or more, more preferably 0.1 mass % to 10 mass %, even more preferably 0.1 mass % to 5 mass %, and particularly preferably 0.1 mass % to 1 mass %, relative to the total mass of the negative photosensitive resin layer N.
[0162] The content ratio of the dye NC means the content ratio of the dye when all of the dye NC contained in the negative photosensitive resin layer N is in a colored state. Hereinafter, a method for quantifying the content ratio of the dye NC will be described using a dye that is colored by radicals as an example. Two solutions are prepared by dissolving a dye (0.001 g) and a dye (0.01 g) in methyl ethyl ketone (100 mL). After adding IRGACURE OXE-01 (BASF) as a photoradical polymerization initiator to each of the obtained solutions, radicals are generated by irradiating light of 365 nm to cause all of the dyes to be in a colored state. Next, the absorbance of each solution at a liquid temperature of 25°C is measured using a spectrophotometer (UV3100, Shimadzu Corporation) in an air atmosphere, and a calibration curve is created. Next, the absorbance of the solution in which all of the dyes have been colored is measured in the same manner as above, except that the negative photosensitive resin layer N (3 g) is dissolved in methyl ethyl ketone instead of the dye. From the absorbance of the obtained solution containing the negative photosensitive resin layer N, the content of the dye contained in the negative photosensitive resin layer N is calculated based on a calibration curve.
[0163] <<Surfactants>> From the viewpoint of thickness uniformity, the negative photosensitive resin layer N preferably contains a surfactant. Examples of the surfactant include anionic surfactants, cationic surfactants, nonionic surfactants, and amphoteric surfactants, and nonionic surfactants are preferred.
[0164] Examples of the nonionic surfactant include polyoxyethylene higher alkyl ether compounds, polyoxyethylene higher alkyl phenyl ether compounds, higher fatty acid diester compounds of polyoxyethylene glycol, silicone-based nonionic surfactants, and fluorine-based nonionic surfactants.
[0165] The negative photosensitive resin layer N preferably contains a fluorine-based nonionic surfactant in terms of better resolution. It is believed that the negative photosensitive resin layer N contains a fluorine-based nonionic surfactant, which suppresses the penetration of the etching solution into the negative photosensitive resin layer N and reduces side etching. Examples of commercially available fluorine-based nonionic surfactants include Megafac (registered trademark) F-551, F-552 (DIC Corporation), and Megafac F-554 (DIC Corporation).
[0166] Examples of the surfactant include those described in paragraphs 0120 to 0125 of International Publication No. 2018 / 179640, those described in paragraph 0017 of Japanese Patent No. 4,502,784, and those described in paragraphs 0060 to 0071 of JP-A-2009-237362.
[0167] The negative photosensitive resin layer N may contain one or more types of surfactants.
[0168] The content of the surfactant is preferably 0.001% by mass to 10% by mass, and more preferably 0.01% by mass to 3% by mass, based on the total mass of the negative photosensitive resin layer N.
[0169] <<Additives>> Examples of the additives include radical polymerization inhibitors, sensitizers, plasticizers, heterocyclic compounds, resins other than those mentioned above, and solvents. The negative photosensitive resin layer N may contain one or more kinds of additives.
[0170] The negative photosensitive resin layer N may contain a radical polymerization inhibitor. Examples of the radical polymerization inhibitor include the thermal polymerization inhibitors described in paragraph 0018 of Japanese Patent No. 4502784. The radical polymerization inhibitor is preferably phenothiazine, phenoxazine, or 4-methoxyphenol. Examples of the radical polymerization inhibitor other than the above include naphthylamine, cuprous chloride, nitrosophenylhydroxyamine aluminum salt, and diphenylnitrosamine. In order not to impair the sensitivity of the negative photosensitive resin layer N, it is preferable to use nitrosophenylhydroxyamine aluminum salt as the radical polymerization inhibitor.
[0171] The total content ratio of the radical polymerization inhibitor, the benzotriazole compound, and the carboxybenzotriazole compound is preferably 0.01% by mass to 3% by mass, and more preferably 0.05% by mass to 1% by mass, relative to the total mass of the negative photosensitive resin layer N. It is preferable to set the total content ratio of the above-mentioned components to 0.01% by mass or more from the viewpoint of imparting storage stability to the negative photosensitive resin layer N. On the other hand, it is preferable to set the total content ratio of the above-mentioned components to 3% by mass or less from the viewpoints of maintaining sensitivity and suppressing decolorization of the dye.
[0172] The negative photosensitive resin layer N may contain a sensitizer. The sensitizer is not limited, and a known sensitizer can be used. In addition, a dye and a pigment can be used as the sensitizer. Examples of the sensitizer include a dialkylaminobenzophenone compound, a pyrazoline compound, an anthracene compound, a coumarin compound, a xanthone compound, a thioxanthone compound, an acridone compound, an oxazole compound, a benzoxazole compound, a thiazole compound, a benzothiazole compound, a triazole compound (e.g., 1,2,4-triazole), a stilbene compound, a triazine compound, a thiophene compound, a naphthalimide compound, a triarylamine compound, and an aminoacridine compound.
[0173] The negative photosensitive resin layer N may contain one or more types of sensitizers.
[0174] When the negative photosensitive resin layer N contains a sensitizer, the content of the sensitizer can be appropriately selected depending on the purpose. From the viewpoints of improving the sensitivity to the light source and improving the curing rate by balancing the polymerization rate and chain transfer, the content of the sensitizer is preferably 0.01% by mass to 5% by mass, and more preferably 0.05% by mass to 1% by mass, relative to the total mass of the negative photosensitive resin layer N.
[0175] The negative photosensitive resin layer N may contain at least one selected from the group consisting of a plasticizer and a heterocyclic compound. Examples of the plasticizer and the heterocyclic compound include the compounds described in paragraphs 0097 to 0103 and paragraphs 0111 to 0118 of WO 2018 / 179640.
[0176] The negative photosensitive resin layer N may contain a resin other than those mentioned above. Examples of resins other than those mentioned above include acrylic resins, styrene-acrylic copolymers (limited to copolymers having a styrene content of 40 mass% or less), polyurethane resins, polyvinyl alcohol, polyvinyl formal, polyamide resins, polyester resins, polyamide resins, epoxy resins, polyacetal resins, polyhydroxystyrene resins, polyimide resins, polybenzoxazole resins, polysiloxane resins, polyethyleneimines, polyallylamine, and polyalkylene glycols.
[0177] The negative photosensitive resin layer N may contain a solvent. When the negative photosensitive resin layer N is formed from a photosensitive resin composition containing a solvent, the solvent may remain in the negative photosensitive resin layer N. The solvent will be described later.
[0178] The negative photosensitive resin layer N may contain, as an additive, at least one selected from the group consisting of metal oxide particles, antioxidants, dispersants, acid multipliers, development accelerators, conductive fibers, thermal radical polymerization initiators, thermal acid generators, UV absorbers, thickeners, crosslinkers, organic suspending agents, and inorganic suspending agents. The additives are described, for example, in paragraphs 0165 to 0184 of JP 2014-85643 A. The contents of the above publications are incorporated herein by reference.
[0179] -Impurities, etc.- The negative photosensitive resin layer N may contain a predetermined amount of impurities. Specific examples of impurities include sodium, potassium, magnesium, calcium, iron, manganese, copper, aluminum, titanium, chromium, cobalt, nickel, zinc, tin, halogens, and ions thereof. Among the above, halide ions, sodium ions, and potassium ions are easily mixed in as impurities, so the following contents are preferable.
[0180] The content of impurities in the negative photosensitive resin layer N is preferably 80 ppm or less, more preferably 10 ppm or less, and even more preferably 2 ppm or less, by mass. The content of impurities in the negative photosensitive resin layer N can be 1 ppb or more, or 0.1 ppm or more, by mass.
[0181] Methods for keeping the amount of impurities within the above range include selecting raw materials with low impurity content as raw materials for the negative photosensitive resin layer N, preventing impurities from being mixed in when forming the negative photosensitive resin layer N, and cleaning the manufacturing equipment to remove impurities. By such methods, the amount of impurities can be kept within the above range.
[0182] The amount of impurities can be determined by known methods, such as ICP (Inductively Coupled Plasma) emission spectrometry, atomic absorption spectrometry, or ion chromatography.
[0183] The content of benzene, formaldehyde, trichloroethylene, 1,3-butadiene, carbon tetrachloride, chloroform, N,N-dimethylformamide, N,N-dimethylacetamide, and hexane in the negative photosensitive resin layer N is preferably small. The content of the above-mentioned compounds in the negative photosensitive resin layer N is preferably 100 ppm or less, more preferably 20 ppm or less, and even more preferably 4 ppm or less, based on mass. The content of the above-mentioned compounds in the negative photosensitive resin layer N can be 10 ppb or more, or 100 ppb or more, based on mass. The content of the above-mentioned compounds can be suppressed in the same manner as the above-mentioned metal impurities. In addition, they can be quantified by a known measurement method.
[0184] The water content in the negative photosensitive resin layer N is preferably 0.01% by mass to 1.0% by mass, and more preferably 0.05% by mass to 0.5% by mass, from the viewpoint of improving reliability and lamination properties.
[0185] -Thickness- The thickness of the negative photosensitive resin layer N may be determined, for example, according to the thickness of the resin pattern 2 to be formed in the developing step described below. The thickness of the negative photosensitive resin layer N may be determined, for example, in the range of 1 μm to 100 μm.
[0186] -Transmittance- In the negative photosensitive resin layer N, the transmittance of light having a wavelength of 365 nm is preferably 10% or more, more preferably 30% or more, and particularly preferably 50% or more, from the viewpoint of superior adhesion. There is no upper limit to the transmittance. In the negative photosensitive resin layer N, the transmittance of light having a wavelength of 365 nm is preferably 99.9% or less.
[0187] The preparation step preferably includes a step of preparing a laminate precursor having a transparent substrate and a light-shielding pattern 1 on the transparent substrate, and a step of forming the negative photosensitive resin layer N on the transparent substrate and the light-shielding pattern 1. In the step of forming the negative photosensitive resin layer N, it is preferable to form the negative photosensitive resin layer N using a photosensitive transfer material (also referred to as a "dry film"). That is, the negative photosensitive resin layer N is preferably a layer formed from a photosensitive transfer material.
[0188] The preparation step preferably includes a step of preparing a transparent substrate, a step of forming a light-shielding pattern 1 on the transparent substrate, and a step of forming a negative photosensitive resin layer N on the transparent substrate and the light-shielding pattern 1. The step of forming the light-shielding pattern 1 preferably includes a step of forming a light-shielding layer on the transparent substrate, a step of forming a photosensitive resin layer on the light-shielding layer, a step of forming a resist pattern by exposing and developing the photosensitive resin layer, and a step of removing the light-shielding layer not covered by the resist pattern. In the step of forming the negative photosensitive resin layer N, the negative photosensitive resin layer N is preferably formed using a photosensitive transfer material.
[0189] The preparation process may include, for example, a process of preparing a transparent substrate, a process of forming a light-shielding pattern 1 on the transparent substrate, and a process of forming a negative-type photosensitive resin layer N on the transparent substrate and the light-shielding pattern 1.
[0190] The preparation step may include, for example, an embodiment including a step of preparing a laminate precursor having a transparent substrate and a light-shielding layer on the transparent substrate, a step of forming a light-shielding pattern 1 from the light-shielding layer, and a step of forming a negative photosensitive resin layer N on the transparent substrate and the light-shielding pattern 1. The light-shielding layer is a layer that is a material for the light-shielding pattern 1. A method for producing a laminate precursor having a transparent substrate and a light-shielding layer may include, for example, a method of forming a light-shielding layer on a transparent substrate.
[0191] Further, the preparation step may include, for example, an embodiment including a step of forming a light-shielding layer on one surface of a transparent substrate, a step of forming a photoresist layer on the light-shielding layer, a step of exposing and developing the photoresist layer to form a resist pattern, and a step of etching the light-shielding layer to form the light-shielding pattern 1. There are no particular limitations on the method for forming the photoresist layer, and known photoresist compositions and photosensitive transfer materials can be used.
[0192] -Method for forming light-shielding pattern 1- A method for forming the light-shielding pattern 1 will now be described. The light-shielding pattern 1 can be formed, for example, by forming a light-shielding layer on a transparent substrate and then processing the light-shielding layer into a pattern.
[0193] Examples of the method for forming the light-shielding layer include sputtering and plating. In sputtering, for example, a layer (light-shielding layer) containing Cu, Ti, or Ni can be formed on the transparent substrate. Among the above metals, Cu, which has low electrical resistance and is inexpensive, is preferable. The component of the layer (light-shielding layer) formed by sputtering may be Ni, Al, Nb, W, Ni-P, or Ni-B. Examples of plating include electroless plating. Known methods can be used for electroless plating. For example, in electroless copper plating, copper can be precipitated on the transparent substrate by the reaction between copper ions and a reducing agent. The catalyst used in electroless plating is preferably a mixed catalyst of palladium and tin. The primary particle diameter of the catalyst is preferably 10 nm or less. The plating solution used in electroless plating preferably contains hypophosphorous acid as a reducing agent. Examples of plating include plating described in the section "Pattern 3 Formation Process" below. The structure of the light-shielding layer may be a single-layer structure or a multi-layer structure. By forming a light-shielding layer having a multi-layer structure, a conductive pattern having a multi-layer structure can be formed. Examples of a method for forming each layer included in the light-shielding layer having a multi-layer structure include electroless plating, sputtering, vapor deposition, and application of a coupling agent.
[0194] As a method for processing the light-shielding layer into a pattern, for example, photolithography can be mentioned. As the photolithography, a known photolithography can be used. For example, a photosensitive resin layer is formed on the light-shielding layer, and then a resist pattern is formed by exposing and developing the photosensitive resin layer, and then the light-shielding layer that is not covered by the resist pattern is removed, thereby forming the light-shielding pattern.
[0195] The type of the photosensitive resin layer formed on the light-shielding layer is not limited. The photosensitive resin layer may be a positive photosensitive resin layer or a negative photosensitive resin layer. The negative photosensitive resin layer may be, for example, the negative photosensitive resin layer described in the above section "Negative Photosensitive Resin Layer N". Examples of the method for forming the photosensitive resin layer include a method using a photosensitive resin composition and a method using a photosensitive transfer material. Examples of the method using the photosensitive resin composition include a method in which a photosensitive resin composition is applied onto the light-shielding layer and then the photosensitive resin composition is dried. The photosensitive resin composition is a composition containing a material for the photosensitive resin layer. Examples of the method using the photosensitive transfer material include a method in which a photosensitive resin layer is disposed on the light-shielding layer by laminating a photosensitive transfer material having a photosensitive resin layer and the light-shielding layer. For the method of forming the negative photosensitive resin layer, the section "Method of forming negative photosensitive resin layer N" below can be referred to.
[0196] The method of exposing the photosensitive resin layer is not limited as long as it is a method capable of forming an exposed portion and a non-exposed portion in the photosensitive resin layer. A known method can be used as the exposure method. The region of the photosensitive resin layer to be exposed may be determined according to the shape of the intended light-shielding pattern. For the exposure conditions, the section "Exposure step" below can be referred to.
[0197] The developing method of the photosensitive resin layer is not limited as long as it is a method capable of processing the photosensitive resin layer into a pattern by removing the exposed or unexposed parts of the photosensitive resin layer. In the development of a negative photosensitive resin layer, the unexposed parts of the negative photosensitive resin layer are removed. In the development of a positive photosensitive resin layer, the exposed parts of the positive photosensitive resin layer are removed. As the developing method, a known method can be used. For the developing conditions, the section "Developing step" below can be referred to.
[0198] A known method can be used to remove the light-shielding layer not covered by the resist pattern (i.e., the exposed light-shielding layer). For example, when the light-shielding layer contains a metal, the light-shielding layer not covered by the resist pattern can be removed by etching. Examples of the etching include wet etching and dry etching. The etching is preferably wet etching. Wet etching is etching using a chemical called an etching solution. Examples of the etching solution include an aqueous solution of sulfuric acid and hydrogen peroxide. The composition of the aqueous solution of sulfuric acid and hydrogen peroxide is not limited. Examples of the aqueous solution of sulfuric acid and hydrogen peroxide include an aqueous solution of sulfuric acid and hydrogen peroxide in which the concentration of sulfuric acid is 1% by volume to 10% by volume and the concentration of hydrogen peroxide is 1% by volume to 10% by volume. The temperature of the aqueous solution of sulfuric acid and hydrogen peroxide can be set, for example, in the range of 20° C. to 35° C. The immersion time in the aqueous solution of sulfuric acid and hydrogen peroxide can be set, for example, in the range of 1 minute to 10 minutes. When the light-shielding layer contains copper, the sulfuric acid-hydrogen peroxide aqueous solution can be used until the concentration of copper dissolved in the sulfuric acid-hydrogen peroxide aqueous solution reaches, for example, 50 g / L. The etching solution can also be, for example, a cupric chloride solution. The composition of the cupric chloride solution is not limited. As the cupric chloride solution, for example, a solution containing 20 mass % to 35 mass % of cupric chloride and 1 mass % to 7 mass % of chlorine can be preferably used. However, the etching conditions are not limited to the above conditions. For example, the temperature of the etching solution and the immersion time in the etching solution may be determined according to the composition of the light-shielding layer, the thickness of the light-shielding layer, and the type of the etching solution.
[0199] The laminate may have an adhesive layer between the transparent substrate and the light-shielding pattern 1. The adhesive layer may be formed, for example, by forming the adhesive layer on the transparent substrate before forming the light-shielding pattern 1. Examples of the method for forming the adhesive layer include electroless plating, sputtering, and vapor deposition. Examples of the method for forming the adhesive layer include a method including coating, drying, and sintering of a metal particle dispersion liquid in which metal particles are dispersed.
[0200] In the method for producing the laminate, the surface of the transparent substrate may be roughened by a desmear treatment, if necessary, before forming the adhesive layer and the light-shielding pattern. Examples of the desmear treatment liquid (oxidizing roughening liquid) include a chromium / sulfuric acid roughening liquid, an alkaline permanganate roughening liquid (e.g., a sodium permanganate roughening liquid), and a sodium fluoride / chromium / sulfuric acid roughening liquid.
[0201] -Method for forming negative photosensitive resin layer N- A description will be given below of a method for forming the negative photosensitive resin layer N. Examples of the method for forming the negative photosensitive resin layer N include a method using a photosensitive resin composition and a method using a photosensitive transfer material.
[0202] -Photosensitive resin composition- An example of a method using a photosensitive resin composition is a method in which the photosensitive resin composition is applied onto a transparent substrate and a light-shielding pattern, and then the photosensitive resin composition is dried.
[0203] The components of the photosensitive resin composition may be determined according to the components of the desired negative photosensitive resin layer N. Preferred components of the photosensitive resin composition include, for example, the components described in the above section on "negative photosensitive resin layer N". The photosensitive resin composition may include, for example, a composition containing a polymer A, a polymerizable compound B, and a photopolymerization initiator. The photosensitive resin composition preferably contains a solvent to adjust the viscosity of the photosensitive resin composition and facilitate the formation of the photosensitive resin layer.
[0204] The solvent is not limited as long as it can dissolve or disperse the components of the photosensitive resin composition (e.g., polymer A, polymerizable compound B, and polymerization initiator), and known solvents can be used. Examples of the solvent include alkylene glycol ether solvents, alkylene glycol ether acetate solvents, alcohol solvents (e.g., methanol and ethanol), ketone solvents (e.g., acetone and methyl ethyl ketone), aromatic hydrocarbon solvents (e.g., toluene), aprotic polar solvents (e.g., N,N-dimethylformamide), cyclic ether solvents (e.g., tetrahydrofuran), ester solvents, amide solvents, and lactone solvents.
[0205] The photosensitive resin composition preferably contains at least one selected from the group consisting of an alkylene glycol ether solvent and an alkylene glycol ether acetate solvent. The photosensitive resin composition more preferably contains at least one selected from the group consisting of an alkylene glycol ether solvent and an alkylene glycol ether acetate solvent, and at least one selected from the group consisting of a ketone solvent and a cyclic ether solvent. The photosensitive resin composition particularly preferably contains at least one selected from the group consisting of an alkylene glycol ether solvent and an alkylene glycol ether acetate solvent, a ketone solvent, and a cyclic ether solvent.
[0206] Examples of alkylene glycol ether solvents include ethylene glycol monoalkyl ethers, ethylene glycol dialkyl ethers, propylene glycol monoalkyl ethers, propylene glycol dialkyl ethers, diethylene glycol dialkyl ethers, dipropylene glycol monoalkyl ethers, and dipropylene glycol dialkyl ethers.
[0207] Alkylene glycol ether acetate solvents include, for example, ethylene glycol monoalkyl ether acetate, propylene glycol monoalkyl ether acetate, diethylene glycol monoalkyl ether acetate, and dipropylene glycol monoalkyl ether acetate.
[0208] As the solvent, the solvents described in paragraphs 0092 to 0094 of International Publication No. 2018 / 179640 and the solvents described in paragraph 0014 of JP-A-2018-177889 may be used. The contents of these are incorporated herein by reference.
[0209] The photosensitive resin composition may contain one or more solvents.
[0210] The content of the solvent in the photosensitive resin composition is preferably 50 parts by mass to 1,900 parts by mass, and more preferably 100 parts by mass to 900 parts by mass, relative to 100 parts by mass of the total solid content in the photosensitive resin composition.
[0211] The method for preparing the photosensitive resin composition is not limited. For example, the photosensitive resin composition may be prepared by dissolving each component in a solvent, and mixing the resulting solutions in a predetermined ratio to prepare the photosensitive resin composition. The photosensitive resin composition is preferably filtered using a filter with a pore size of 0.2 μm to 30 μm before forming the negative photosensitive resin layer.
[0212] The method for applying the photosensitive resin composition is not limited, and any known method can be used, including, for example, slit coating, spin coating, curtain coating, and inkjet coating.
[0213] -Photosensitive transfer material- As a method of using a photosensitive transfer material, for example, a method of laminating a photosensitive transfer material having a negative photosensitive resin layer N with a transparent substrate having a light-shielding pattern, and disposing the negative photosensitive resin layer N on the transparent substrate and the light-shielding pattern can be mentioned. In the method of laminating a photosensitive transfer material having a negative photosensitive resin layer N with a transparent substrate having a light-shielding pattern, it is preferable to laminate the photosensitive transfer material and the transparent substrate, and pressurize and heat them using a means such as a roll. For lamination, a laminator, a vacuum laminator, and an auto-cut laminator that can further increase productivity can be used. Hereinafter, the components of the photosensitive transfer material will be described.
[0214] --Photosensitive resin layer-- The photosensitive transfer material has a negative photosensitive resin layer N. The negative photosensitive resin layer N is as described above in the section "Negative photosensitive resin layer N."
[0215] --Temporary support-- The photosensitive transfer material preferably has a temporary support. The temporary support is a support that can be peeled off from the photosensitive transfer material. The temporary support can support at least the negative photosensitive resin layer N. The temporary support may be peeled off before the exposure step. The temporary support may be peeled off after irradiating light in the exposure step without peeling off the temporary support. By irradiating light without peeling off the temporary support in the exposure step, the influence of dirt and dust in the exposure environment can be avoided.
[0216] As the temporary support, a temporary support having optical transparency can be used. In the present disclosure, "having optical transparency" means that the transmittance of light having a wavelength used for pattern exposure is 50% or more. In the temporary support, the transmittance of light having a wavelength used for pattern exposure (preferably a wavelength of 365 nm) is preferably 60% or more, more preferably 70% or more, from the viewpoint of improving the exposure sensitivity of the negative photosensitive resin layer N.
[0217] Examples of the temporary support include a glass substrate, a resin film, and paper. From the viewpoints of strength, flexibility, and light transmittance, the temporary support is preferably a resin film.
[0218] Examples of the resin film include a polyethylene terephthalate film (i.e., a PET film), a cellulose triacetate film, a polystyrene film, and a polycarbonate film. The resin film is preferably a PET film, and more preferably a biaxially stretched PET film.
[0219] The thickness of the temporary support is not limited. The average thickness of the temporary support may be determined, for example, according to the strength, light transmittance, material, and flexibility required for laminating the photosensitive transfer material and the transparent substrate as the temporary support. The average thickness of the temporary support is preferably 5 μm to 100 μm. Furthermore, from the viewpoint of ease of handling and versatility, the average thickness of the temporary support is preferably 5 μm to 50 μm, more preferably 5 μm to 20 μm, even more preferably 10 μm to 20 μm, and particularly preferably 10 μm to 16 μm.
[0220] The arithmetic mean roughness Ra of the surface of the temporary support on which the negative photosensitive resin layer N is disposed is preferably 0.1 μm or less, more preferably 0.05 μm or less, and particularly preferably 0.02 μm or less. The lower limit of the arithmetic mean roughness Ra is not limited. The arithmetic mean roughness Ra of the surface of the temporary support on which the negative photosensitive resin layer N is disposed may be determined, for example, in the range of 0 μm or more.
[0221] The arithmetic mean roughness Ra is measured by the following method. A three-dimensional optical profiler (New View7300, manufactured by Zygo) is used to obtain a surface profile of the measurement object under the following conditions. MetroPro ver8.3.2 Microscope Application is used as the measurement and analysis software. Next, the above software is used to display the Surface Map screen, and histogram data is obtained in the Surface Map screen. The arithmetic mean roughness Ra of the surface of the measurement object is obtained from the obtained histogram data. Note that if the surface of the measurement object is in contact with the surface of another layer, the measurement object may be peeled off from the other layer to measure the arithmetic mean roughness Ra of the exposed surface of the measurement object.
[0222] The temporary support (particularly the resin film) is preferably free of, for example, deformations (e.g., wrinkles), scratches, and defects. From the viewpoint of the transparency of the temporary support, it is preferable that the temporary support contains a small number of fine particles, foreign matter, defects, and precipitates. The number of fine particles, foreign matter, and defects having a diameter of 1 μm or more in the temporary support is 50 / 10 mm. 2 It is preferable that the number of pieces is less than 10 pieces / 10 mm. 2 More preferably, 3 pieces / 10 mm or less. 2 More preferably, 0 pieces / 10 mm or less. 2 It is particularly preferred that:
[0223] Preferred embodiments of the temporary support are described, for example, in paragraphs 0017 to 0018 of JP 2014-85643 A, paragraphs 0019 to 0026 of JP 2016-27363 A, paragraphs 0041 to 0057 of WO 2012 / 081680 A, paragraphs 0029 to 0040 of WO 2018 / 179370 A, and paragraphs 0012 to 0032 of JP 2019-101405 A. The contents of these publications are incorporated herein by reference.
[0224] --Cover film-- The photosensitive transfer material may have a cover film (also called a protective film). The cover film can protect the surface of a layer (e.g., a negative photosensitive resin layer N) that contacts the cover film. The photosensitive transfer material preferably includes a temporary support, a negative photosensitive resin layer N, and a cover film in this order. The photosensitive transfer material preferably has a cover film that contacts the surface of the negative photosensitive resin layer N opposite to the side where the temporary support is disposed.
[0225] Examples of the cover film include a resin film and paper. From the viewpoints of strength and flexibility, the cover film is preferably a resin film.
[0226] Examples of the resin film include a polyethylene film, a polypropylene film, a polyethylene terephthalate film, a cellulose triacetate film, a polystyrene film, and a polycarbonate film. The resin film is preferably a polyethylene film, a polypropylene film, or a polyethylene terephthalate film.
[0227] There are no limitations on the thickness of the cover film, and the average thickness of the cover film is preferably 5 μm to 100 μm, more preferably 10 μm to 50 μm, and particularly preferably 10 μm to 20 μm.
[0228] The arithmetic mean roughness Ra of the surface of the cover film on which the negative photosensitive resin layer N is arranged is preferably 0.3 μm or less, more preferably 0.1 μm or less, and particularly preferably 0.05 μm or less, from the viewpoint of superior resolution. When the arithmetic mean roughness of the surface of the cover film on which the negative photosensitive resin layer N is arranged is within the above range, the uniformity of the thickness of the negative photosensitive resin layer and the resin pattern formed is improved. The lower limit of the arithmetic mean roughness Ra is not limited. The arithmetic mean roughness Ra of the surface of the cover film on which the negative photosensitive resin layer N is arranged is preferably 0.001 μm or more. The arithmetic mean roughness Ra of the surface of the cover film on which the negative photosensitive resin layer N is arranged is measured by a method similar to the method for measuring the arithmetic mean roughness Ra described in the above section "Temporary Support".
[0229] --Thermoplastic resin layer-- The photosensitive transfer material according to the present disclosure may have a thermoplastic resin layer N. The photosensitive transfer material preferably has a thermoplastic resin layer between the temporary support and the negative photosensitive resin layer N. By having a thermoplastic resin layer between the temporary support and the negative photosensitive resin layer N, the photosensitive transfer material has improved conformability to the adherend, and the inclusion of air bubbles between the adherend and the photosensitive transfer material is suppressed, resulting in improved adhesion between the layers.
[0230] The thermoplastic resin layer preferably contains an alkali-soluble resin as the thermoplastic resin.
[0231] Examples of alkali-soluble resins include acrylic resins, polystyrene resins, styrene-acrylic copolymers, polyurethane resins, polyvinyl alcohol, polyvinyl formal, polyamide resins, polyester resins, epoxy resins, polyacetal resins, polyhydroxystyrene resins, polyimide resins, polybenzoxazole resins, polysiloxane resins, polyethyleneimines, polyallylamine, and polyalkylene glycols.
[0232] The alkali-soluble resin is preferably an acrylic resin from the viewpoints of developability and adhesion to a layer adjacent to the thermoplastic resin layer. Here, the term "acrylic resin" refers to a resin having at least one selected from the group consisting of a structural unit derived from (meth)acrylic acid, a structural unit derived from a (meth)acrylic acid ester, and a structural unit derived from a (meth)acrylic acid amide.
[0233] In the acrylic resin, the total content ratio of the structural units derived from (meth)acrylic acid, the structural units derived from (meth)acrylic acid esters, and the structural units derived from (meth)acrylic acid amides is preferably 50 mass% or more relative to the total mass of the acrylic resin. In the acrylic resin, the total content ratio of the structural units derived from (meth)acrylic acid and the structural units derived from (meth)acrylic acid esters is preferably 30 mass% to 100 mass%, more preferably 50 mass% to 100 mass%, relative to the total mass of the acrylic resin.
[0234] The alkali-soluble resin is preferably a polymer having an acid group, such as a carboxy group, a sulfo group, a phosphoric acid group, or a phosphonic acid group, with the carboxy group being preferred.
[0235] From the viewpoint of developability, the alkali-soluble resin is preferably an alkali-soluble resin having an acid value of 60 mgKOH / g or more, and more preferably an acrylic resin containing a carboxyl group having an acid value of 60 mgKOH / g or more. The upper limit of the acid value is not limited. The acid value of the alkali-soluble resin is preferably 200 mgKOH / g or less, and more preferably 150 mgKOH / g or less.
[0236] The carboxyl group-containing acrylic resin having an acid value of 60 mgKOH / g or more is not limited, and can be appropriately selected from known resins. Examples of the carboxyl group-containing acrylic resin having an acid value of 60 mgKOH / g or more include the carboxyl group-containing acrylic resin having an acid value of 60 mgKOH / g or more among the polymers described in paragraph 0025 of JP-A-2011-95716, the carboxyl group-containing acrylic resin having an acid value of 60 mgKOH / g or more among the polymers described in paragraphs 0033 to 0052 of JP-A-2010-237589, and the carboxyl group-containing acrylic resin having an acid value of 60 mgKOH / g or more among the binder polymers described in paragraphs 0053 to 0068 of JP-A-2016-224162.
[0237] The content of structural units having a carboxy group in the carboxy group-containing acrylic resin is preferably 5% by mass to 50% by mass, more preferably 10% by mass to 40% by mass, and particularly preferably 12% by mass to 30% by mass, relative to the total mass of the carboxy group-containing acrylic resin.
[0238] From the viewpoints of developability and adhesion to a layer adjacent to the thermoplastic resin layer, the alkali-soluble resin is particularly preferably an acrylic resin having a structural unit derived from (meth)acrylic acid.
[0239] The alkali-soluble resin may have a reactive group. The reactive group may be, for example, a group capable of addition polymerization. Examples of the reactive group include an ethylenically unsaturated group, a polycondensable group (e.g., a hydroxyl group and a carboxyl group), and a polyaddition reactive group (e.g., an epoxy group and a (blocked) isocyanate group).
[0240] The weight average molecular weight (Mw) of the alkali-soluble resin is preferably 1,000 or more, more preferably from 10,000 to 100,000, and particularly preferably from 20,000 to 50,000.
[0241] The thermoplastic resin layer may contain one kind of alkali-soluble resin alone, or two or more kinds of alkali-soluble resins.
[0242] From the viewpoints of developability and adhesion to layers adjacent to the thermoplastic resin layer, the content of the alkali-soluble resin is preferably 10% by mass to 99% by mass, more preferably 20% by mass to 90% by mass, even more preferably 40% by mass to 80% by mass, and particularly preferably 50% by mass to 70% by mass, relative to the total mass of the thermoplastic resin layer.
[0243] The thermoplastic resin layer preferably contains a dye (hereinafter sometimes referred to as "dye B") whose maximum absorption wavelength in the wavelength range of 400 nm to 780 nm during color development is 450 nm or more and whose maximum absorption wavelength changes with an acid, a base, or a radical. Preferred aspects of dye B are the same as those of dye NC described above, except for the points described below.
[0244] From the viewpoints of visibility of exposed areas, visibility of unexposed areas, and resolution, dye B is preferably a dye whose maximum absorption wavelength changes in response to an acid or a radical, and more preferably a dye whose maximum absorption wavelength changes in response to an acid.
[0245] From the viewpoints of visibility of exposed areas, visibility of unexposed areas, and resolution, it is preferable that the thermoplastic resin layer contains, as dye B, a dye whose maximum absorption wavelength changes in response to acid, and a compound that generates acid when exposed to light, as described below.
[0246] The thermoplastic resin layer may contain one type of dye B alone, or two or more types of dye B.
[0247] From the viewpoint of visibility of exposed areas and visibility of non-exposed areas, the content of dye B is preferably 0.2 mass% or more, more preferably 0.2 mass% to 6 mass%, even more preferably 0.2 mass% to 5 mass%, and particularly preferably 0.25 mass% to 3.0 mass%, relative to the total mass of the thermoplastic resin layer.
[0248] Here, the content ratio of dye B means the content ratio of dye when all of the dye B contained in the thermoplastic resin layer is in a colored state. Hereinafter, a method for quantifying the content ratio of dye B will be described using a dye that develops color by radicals as an example. Two solutions are prepared by dissolving dye (0.001 g) and dye (0.01 g) in methyl ethyl ketone (100 mL). IRGACURE OXE-01 (BASF) is added as a photoradical polymerization initiator to each of the obtained solutions, and then 365 nm light is irradiated to generate radicals and cause all of the dyes to develop color. Next, the absorbance of each solution with a liquid temperature of 25°C is measured using a spectrophotometer (UV3100, Shimadzu Corporation) in an air atmosphere, and a calibration curve is created. Next, the absorbance of the solution in which all of the dyes have developed color is measured using the same method as above, except that the thermoplastic resin layer (0.1 g) is dissolved in methyl ethyl ketone instead of the dye. From the absorbance of the obtained solution containing the thermoplastic resin layer, the amount of the dye contained in the thermoplastic resin layer is calculated based on a calibration curve.
[0249] The thermoplastic resin layer may contain a compound that generates an acid, a base, or a radical when exposed to light (hereinafter, may be referred to as "compound C"). Compound C is preferably a compound that generates an acid, a base, or a radical when exposed to actinic rays (e.g., ultraviolet light and visible light). Examples of compound C include known photoacid generators, photobase generators, and photoradical polymerization initiators (photoradical generators). Compound C is preferably a photoacid generator.
[0250] From the viewpoint of resolution, the thermoplastic resin layer preferably contains a photoacid generator. Examples of the photoacid generator include the photocationic polymerization initiator that may be contained in the negative photosensitive resin layer described above, and the preferred aspects are the same as those described below.
[0251] From the viewpoints of sensitivity and resolution, the photoacid generator preferably contains at least one selected from the group consisting of an onium salt compound and an oxime sulfonate compound, and from the viewpoints of sensitivity, resolution and adhesion, it is more preferable that the photoacid generator contains an oxime sulfonate compound.
[0252] The photoacid generator is also preferably a photoacid generator having the following structure:
[0253] [ka]
[0254] The thermoplastic resin layer may contain a photobase generator. Examples of the photobase generator include 2-nitrobenzyl cyclohexyl carbamate, triphenylmethanol, O-carbamoyl hydroxylamide, O-carbamoyl oxime, [[(2,6-dinitrobenzyl)oxy]carbonyl]cyclohexylamine, bis[[(2-nitrobenzyl)oxy]carbonyl]hexane 1,6-diamine, 4-(methylthiobenzoyl)-1-methyl-1-morpholinoethane, (4-morpholinobenzoyl)-1-benzyl-1-diamine, and the like. Methylaminopropane, N-(2-nitrobenzyloxycarbonyl)pyrrolidine, hexaamminecobalt(III) tris(triphenylmethylborate), 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone, 2,6-dimethyl-3,5-diacetyl-4-(2-nitrophenyl)-1,4-dihydropyridine, and 2,6-dimethyl-3,5-diacetyl-4-(2,4-dinitrophenyl)-1,4-dihydropyridine.
[0255] The thermoplastic resin layer may contain a photoradical polymerization initiator. Examples of the photoradical polymerization initiator include the photoradical polymerization initiators that may be contained in the negative photosensitive resin layer described above, and preferred embodiments are also the same.
[0256] The thermoplastic resin layer may contain one or more kinds of compound C.
[0257] From the viewpoints of visibility of exposed areas, visibility of non-exposed areas, and resolution, the content of compound C is preferably 0.1% by mass to 10% by mass, and more preferably 0.5% by mass to 5% by mass, relative to the total mass of the thermoplastic resin layer.
[0258] The thermoplastic resin layer preferably contains a plasticizer from the viewpoints of resolution, adhesion to layers adjacent to the thermoplastic resin layer, and developability.
[0259] The molecular weight of the plasticizer (when it is an oligomer or polymer, it means the weight average molecular weight (Mw). The same applies hereinafter in this paragraph) is preferably smaller than the molecular weight of the alkali-soluble resin. The molecular weight of the plasticizer is preferably 200 to 2,000.
[0260] The plasticizer is not limited as long as it is a compound that is compatible with the alkali-soluble resin and exhibits plasticity.From the viewpoint of imparting plasticity, the plasticizer is preferably a compound having an alkyleneoxy group in the molecule, more preferably a polyalkylene glycol compound.The alkyleneoxy group contained in the plasticizer preferably has a polyethyleneoxy structure or a polypropyleneoxy structure.
[0261] From the viewpoints of resolution and storage stability, the plasticizer preferably contains a (meth)acrylate compound. From the viewpoints of compatibility, resolution, and adhesion to a layer adjacent to the thermoplastic resin layer, it is more preferable that the alkali-soluble resin is an acrylic resin and the plasticizer contains a (meth)acrylate compound.
[0262] Examples of the (meth)acrylate compound used as the plasticizer include the (meth)acrylate compounds described in the above section on "polymerizable compound B". In the photosensitive transfer material, when the thermoplastic resin layer and the negative photosensitive resin layer are disposed in direct contact with each other, it is preferable that the thermoplastic resin layer and the negative photosensitive resin layer each contain the same (meth)acrylate compound. This is because the thermoplastic resin layer and the negative photosensitive resin layer each contain the same (meth)acrylate compound, thereby suppressing component diffusion between layers and improving storage stability.
[0263] When the thermoplastic resin layer contains a (meth)acrylate compound as a plasticizer, it is preferable that the (meth)acrylate compound does not polymerize even in the exposed area after exposure, from the viewpoint of adhesion to layers adjacent to the thermoplastic resin layer.
[0264] In one embodiment, the (meth)acrylate compound used as a plasticizer is preferably a (meth)acrylate compound having two or more (meth)acryloyl groups in one molecule, from the viewpoints of resolution, adhesion to a layer adjacent to the thermoplastic resin layer, and developability.
[0265] In an embodiment, the (meth)acrylate compound used as the plasticizer is preferably a (meth)acrylate compound having an acid group, or a urethane (meth)acrylate compound.
[0266] The thermoplastic resin layer may contain one or more kinds of plasticizers.
[0267] From the viewpoints of resolution, adhesion to layers adjacent to the thermoplastic resin layer, and developability, the content of the plasticizer is preferably 1% by mass to 70% by mass, more preferably 10% by mass to 60% by mass, and particularly preferably 20% by mass to 50% by mass, relative to the total mass of the thermoplastic resin layer.
[0268] From the viewpoint of thickness uniformity, the thermoplastic resin layer preferably contains a surfactant. Examples of the surfactant include the surfactants that may be contained in the negative photosensitive resin layer N described above, and the preferred embodiments are the same.
[0269] The thermoplastic resin layer may contain one or more types of surfactants.
[0270] The content of the surfactant is preferably from 0.001% by mass to 10% by mass, and more preferably from 0.01% by mass to 3% by mass, based on the total mass of the thermoplastic resin layer.
[0271] The thermoplastic resin layer may contain a sensitizer, for example, the sensitizers that may be contained in the negative photosensitive resin layer described above.
[0272] The thermoplastic resin layer may contain one or more types of sensitizers.
[0273] From the viewpoints of improving sensitivity to the light source, visibility of exposed areas, and visibility of non-exposed areas, the content of the sensitizer is preferably 0.01% by mass to 5% by mass, and more preferably 0.05% by mass to 1% by mass, relative to the total mass of the thermoplastic resin layer.
[0274] The thermoplastic resin layer may contain known additives, if necessary, in addition to the above components.
[0275] The thermoplastic resin layer is described in paragraphs 0189 to 0193 of JP 2014-85643 A, the contents of which are incorporated herein by reference.
[0276] The thickness of the thermoplastic resin layer is not limited. From the viewpoint of adhesion with the layer adjacent to the thermoplastic resin layer, the average thickness of the thermoplastic resin layer is preferably 1 μm or more, more preferably 2 μm or more. The upper limit of the average thickness of the thermoplastic resin layer is not limited. From the viewpoint of developability and resolution, the average thickness of the thermoplastic resin layer is preferably 20 μm or less, more preferably 10 μm or less, and particularly preferably 5 μm or less.
[0277] The method for forming the thermoplastic resin layer is not limited as long as it is a method capable of forming a layer containing the above-mentioned components. For example, the method for forming the thermoplastic resin layer includes a method of applying a thermoplastic resin composition to the surface of a temporary support and drying the coating of the thermoplastic resin composition.
[0278] The thermoplastic resin composition may be, for example, a composition containing the above-mentioned components. The thermoplastic resin composition preferably contains a solvent to adjust the viscosity of the thermoplastic resin composition and facilitate the formation of the thermoplastic resin layer.
[0279] The solvent contained in the thermoplastic resin composition is not limited as long as it can dissolve or disperse the components contained in the thermoplastic resin layer. Examples of the solvent include the solvents that may be contained in the photosensitive resin composition described above, and the preferred embodiments are the same.
[0280] The thermoplastic resin composition may contain one or more solvents.
[0281] The content of the solvent in the thermoplastic resin composition is preferably 50 to 1,900 parts by mass, and more preferably 100 to 900 parts by mass, relative to 100 parts by mass of the total solid content in the thermoplastic resin composition.
[0282] The preparation of the thermoplastic resin composition and the formation of the thermoplastic resin layer may be performed in accordance with the above-mentioned method for preparing the photosensitive resin composition and the method for forming the negative photosensitive resin layer N. For example, a solution in which each component contained in the thermoplastic resin layer is dissolved in a solvent is prepared in advance, and the obtained solutions are mixed in a predetermined ratio to prepare a thermoplastic resin composition, and then the obtained thermoplastic resin composition is applied to the surface of a temporary support, and the coating film of the thermoplastic resin composition is dried to form a thermoplastic resin layer. In addition, after forming a negative photosensitive resin layer N on a cover film, a thermoplastic resin layer may be formed on the surface of the negative photosensitive resin layer N.
[0283] --Middle class-- The photosensitive transfer material preferably has an intermediate layer between the thermoplastic resin layer and the negative photosensitive resin layer N. The intermediate layer can suppress mixing of components when forming a plurality of layers and during storage.
[0284] The intermediate layer is preferably a water-soluble layer from the viewpoints of developability and suppressing mixing of components when applying multiple layers and during storage after application. In the present disclosure, "water-soluble" means that the solubility in 100 g of water at pH 7.0 and a liquid temperature of 22°C is 0.1 g or more.
[0285] An example of the intermediate layer is an oxygen barrier layer having an oxygen barrier function, which is described as a "separation layer" in JP-A-5-72724. When the intermediate layer is an oxygen barrier layer, the sensitivity during exposure is improved, and the time load of the exposure machine is reduced, resulting in improved productivity. The oxygen barrier layer used as the intermediate layer may be appropriately selected from known layers. The oxygen barrier layer used as the intermediate layer is preferably an oxygen barrier layer that exhibits low oxygen permeability and disperses or dissolves in water or an alkaline aqueous solution (a 1% by mass aqueous solution of sodium carbonate at 22°C).
[0286] The intermediate layer preferably contains a resin. Examples of the resin contained in the intermediate layer include polyvinyl alcohol resins, polyvinylpyrrolidone resins, cellulose resins, acrylamide resins, polyethylene oxide resins, gelatin, vinyl ether resins, polyamide resins, and copolymers thereof. The resin contained in the intermediate layer is preferably a water-soluble resin.
[0287] From the viewpoint of suppressing mixing of components between multiple layers, it is preferable that the resin contained in the intermediate layer is a resin different from both the polymer A contained in the negative photosensitive resin layer N and the thermoplastic resin (alkali-soluble resin) contained in the thermoplastic resin layer.
[0288] From the viewpoints of oxygen barrier properties and suppressing mixing of components when multiple layers are applied and during storage after application, the intermediate layer preferably contains polyvinyl alcohol, and more preferably contains polyvinyl alcohol and polyvinylpyrrolidone.
[0289] The intermediate layer may contain one type of resin alone, or two or more types of resins.
[0290] From the viewpoints of oxygen barrier properties and suppressing mixing of components when multiple layers are applied and during storage after application, the resin content in the intermediate layer is preferably 50% by mass to 100% by mass, more preferably 70% by mass to 100% by mass, even more preferably 80% by mass to 100% by mass, and particularly preferably 90% by mass to 100% by mass, relative to the total mass of the intermediate layer.
[0291] Furthermore, the intermediate layer may contain additives as necessary, such as a surfactant.
[0292] The thickness of the intermediate layer is not limited. The average thickness of the intermediate layer is preferably 0.1 μm to 5 μm, and more preferably 0.5 μm to 3 μm. By having the thickness of the intermediate layer within the above range, the oxygen barrier properties are not reduced, mixing of components during formation of multiple layers and during storage can be suppressed, and an increase in the time required to remove the intermediate layer during development can be suppressed.
[0293] The method for forming the intermediate layer is not limited as long as it is a method capable of forming a layer containing the above-mentioned components. For example, the method for forming the intermediate layer includes a method of applying an intermediate layer composition to the surface of the thermoplastic resin layer or the negative photosensitive resin layer N, and then drying the coating of the intermediate layer composition.
[0294] The intermediate layer composition may be, for example, a composition containing a resin and any additive. The intermediate layer composition preferably contains a solvent to adjust the viscosity of the intermediate layer composition and facilitate the formation of the intermediate layer. The solvent is not limited as long as it can dissolve or disperse the resin. The solvent is preferably at least one selected from the group consisting of water and water-miscible organic solvents, and more preferably water or a mixed solvent of water and a water-miscible organic solvent. Examples of the water-miscible organic solvent include alcohols having 1 to 3 carbon atoms, acetone, ethylene glycol, and glycerin. The water-miscible organic solvent is preferably an alcohol having 1 to 3 carbon atoms, and more preferably methanol or ethanol.
[0295] The photosensitive transfer material may further include other layers such as a refractive index adjusting layer. The refractive index adjusting layer is not particularly limited, and any known refractive index adjusting layer can be used. From the viewpoint of suppressing visibility of the wiring, the refractive index of the refractive index-matching layer is preferably higher than the refractive index of the photosensitive layer. The refractive index of the refractive index adjusting layer is preferably 1.50 or more, more preferably 1.55 or more, further preferably 1.60 or more, and particularly preferably 1.70 or more. The upper limit of the refractive index of the refractive index adjusting layer is not particularly limited, but is preferably 2.10 or less, more preferably 1.85 or less, further preferably 1.78 or less, and particularly preferably 1.74 or less. The thickness of the refractive index adjusting layer is not particularly limited. The thickness of the refractive index adjusting layer is preferably 50 nm or more and 500 nm or less, more preferably 55 nm or more and 110 nm or less, and further preferably 60 nm or more and 100 nm or less. The method for controlling the refractive index of the refractive index adjusting layer is not particularly limited, and examples thereof include a method of using a resin having a predetermined refractive index alone, a method of using a resin and metal oxide particles or metal particles, a method of using a complex of a metal salt and a resin, and the like. The type of metal oxide particles is not particularly limited, and known metal oxide particles can be used. Specifically, the metal oxide particles are preferably at least one selected from the group consisting of zirconium oxide particles (ZrO2 particles), Nb2O5 particles, titanium oxide particles (TiO2 particles), and silicon dioxide particles (SiO2 particles). Among these, the metal oxide particles are more preferably at least one type selected from the group consisting of zirconium oxide particles and titanium oxide particles, from the viewpoint of facilitating adjustment of the refractive index of the second resin layer to 1.6 or more, for example.
[0296] --Average thickness-- The average thickness of the photosensitive transfer material is preferably 5 μm to 55 μm, more preferably 10 μm to 50 μm, and particularly preferably 20 μm to 40 μm. The average thickness of the photosensitive transfer material is measured by a method similar to the method for measuring the average thickness of the transparent substrate described above.
[0297] --shape-- The shape of the photosensitive transfer material is not limited. From the viewpoints of versatility and transportability, the shape of the photosensitive transfer material is preferably a roll. The photosensitive transfer material can be rolled by winding it up.
[0298] -Production method of photosensitive transfer material-- The method for producing the photosensitive transfer material is not limited. For example, the method for producing the photosensitive transfer material includes a method including a step of forming a negative photosensitive resin layer N by applying a photosensitive resin composition on a temporary support, and a step of disposing a cover film on the negative photosensitive resin layer N. In the above method, the photosensitive resin composition applied on the temporary support may be dried as necessary. The drying method is not limited, and a known drying method can be used. For example, a method for disposing a cover film on the negative photosensitive resin layer N includes a method of pressing a cover film onto the negative photosensitive resin layer N.
[0299] <Exposure process> The method for producing a structure according to the present disclosure includes a step of irradiating a part of the negative photosensitive resin layer N with light from the surface of the transparent substrate opposite to the surface on which the light-shielding pattern 1 is provided (exposure step). In the exposure step, light is applied from the surface of the transparent substrate opposite to the surface on which the light-shielding pattern 1 is provided. In the present disclosure, the term "surface on which the light-shielding pattern 1 of the transparent substrate is provided" refers to the surface of the transparent substrate on the side having the light-shielding pattern 1. For example, in FIG. 1(b), the term "surface on which the light-shielding pattern 1 of the transparent substrate is provided" refers to the surface of the transparent substrate 10 in contact with the light-shielding pattern 20, that is, the surface facing the opposite side to the exposed surface 10a. For example, as shown in FIG. 1(b), when light is applied to the surface opposite to the surface facing the light-shielding pattern of the transparent substrate, a part of the light reaching the negative photosensitive resin layer N is blocked by the light-shielding pattern, and a part of the negative photosensitive resin layer N can be selectively exposed. The exposed portion of the negative photosensitive resin layer N is less soluble in a developer. In addition, compared to the case where light is irradiated from the negative photosensitive resin layer N toward the transparent substrate, by irradiating light to the surface of the transparent substrate opposite to the surface facing the light-shielding pattern, the curing of the negative photosensitive resin layer N in the vicinity of the transparent substrate can be promoted. As a result, the resolution of the resin pattern can be improved in the developing process described later. In addition, a resin pattern having sidewalls with high linearity can be formed.
[0300] The light source used in the exposure step may be any light source that irradiates light with a wavelength (e.g., 365 nm or 405 nm) that can expose the negative photosensitive resin layer N. Specific examples of the light source include an ultra-high pressure mercury lamp, a high pressure mercury lamp, a metal halide lamp, and an LED (Light Emitting Diode).
[0301] The light irradiated in the exposure step preferably includes a wavelength in the wavelength range of 200 nm to 1,500 nm, more preferably includes a wavelength in the wavelength range of 250 nm to 450 nm, preferably includes a wavelength in the wavelength range of 300 nm to 410 nm, and more preferably includes a wavelength of 365 nm.
[0302] The exposure dose was 5 mJ / cm 2 ~200mJ / cm 2and preferably 10 mJ / cm 2 ~100mJ / cm 2 It is more preferable that:
[0303] In the exposure process, since a portion of the negative photosensitive resin layer N can be selectively exposed by the light-shielding pattern, light may be irradiated onto the entire surface of the transparent substrate opposite the surface on which the light-shielding pattern 1 is provided.
[0304] <Developing process> The method for producing a structure according to the present disclosure includes a step of developing the negative photosensitive resin layer N irradiated with light to form a resin pattern 2 on the transparent substrate (development step). In the development step, the negative photosensitive resin layer N is developed to form a resin pattern 2 in the region defined by the transparent substrate and the light-shielding pattern. For example, as shown in Fig. 1(c), in the development step, the non-exposed portion of the negative photosensitive resin layer N is removed to form a resin pattern having a shape corresponding to the shape of the exposed portion of the negative photosensitive resin layer N.
[0305] As the developing method, a known method can be used. The negative photosensitive resin layer N can be developed, for example, using a developer. The type of developer is not limited as long as it can remove the unexposed portion of the negative photosensitive resin layer N. As the developer, a known developer (for example, the developer described in JP-A-5-72724) can be used.
[0306] The developer is preferably an alkaline aqueous developer containing a compound having a pKa of 7 to 13 at a concentration of 0.05 mol / L to 5 mol / L. The developer may contain a water-soluble organic solvent and / or a surfactant. The developer is also preferably the developer described in paragraph 0194 of WO2015 / 093271.
[0307] The development method is not particularly limited, and may be any of paddle development, shower development, shower and spin development, and dip development. Shower development is a development treatment in which a developer is sprayed by shower onto the photosensitive resin layer after exposure, thereby removing the exposed or unexposed area.
[0308] After the development step, it is preferable to remove development residues by spraying a cleaning agent by showering and scrubbing with a brush.
[0309] The temperature of the developer is not limited, but is preferably 20°C to 40°C.
[0310] The average thickness of the resin pattern 2 is preferably larger than that of the light-shielding pattern 1. When the average thickness of the resin pattern 2 is larger than that of the light-shielding pattern, a thick light-shielding pattern 1 can be formed. The ratio of the average thickness of the resin pattern 2 to that of the light-shielding pattern 1 ([average thickness of the resin pattern 2] / [average thickness of the light-shielding pattern 1]) is preferably 1.1 or more, more preferably 1.5 or more, and particularly preferably 3 or more. The ratio of the average thickness of the resin pattern 2 to that of the light-shielding pattern 1 may be 4, 5, or 10. The average thickness of the resin pattern 2 is estimated by a method similar to the method for measuring the average thickness of the transparent substrate described above.
[0311] The average thickness of the resin pattern 2 is preferably 1 μm or more, more preferably 2 μm or more, and particularly preferably more than 2 μm. Furthermore, the average thickness of the resin pattern is preferably 3 μm or more, more preferably 5 μm or more, and particularly preferably 10 μm or more. There is no upper limit to the thickness of the resin pattern 2. The average thickness of the resin pattern may be determined, for example, in the range of 100 μm or less.
[0312] The average width of the resin pattern 2 is preferably 50 μm or less, and more preferably 5 μm or less. The average width of the resin pattern 2 is preferably 0.3 μm or more, and more preferably 0.5 μm or more. The average width of the resin pattern 2 is measured by a method similar to the method for measuring the average width of the light-shielding pattern 1.
[0313] <Pattern 3 formation process> The method for producing a structure according to the present disclosure includes a step of forming a pattern 3 in a region defined by the light-shielding pattern 1 and the resin pattern 2 (a pattern 3 forming step). In the pattern 3 forming step, the pattern 3 is formed on the light-shielding pattern 1. For example, as shown in Fig. 1(d), in the pattern 3 forming step, the pattern 3 is formed in a region defined by the light-shielding pattern 1 and the resin pattern 2. In order to more effectively exert the effects of the present disclosure, it is preferable that pattern 3 be conductive. In addition, from the viewpoint of pattern formability and dimensional stability of the resulting pattern 3, it is preferable that the average thickness of the light-shielding pattern 1 is greater than that of the pattern 3.
[0314] A known method can be used as a method for forming the pattern 3. A material having conductivity suitable for the application can be used as a material for the conductive pattern 3. The material for the conductive pattern 3 preferably contains Cu or a Cu alloy. The Cu alloy is preferably an alloy of Cu and at least one selected from the group consisting of Ni, Mo, Ta, Ti, V, Cr, Fe, Mn, Co, and W. The pattern 3 formed using the above-mentioned material contains the above-mentioned metal element. The pattern 3 obtained in the pattern 3 formation step may be a conductive pattern made of Cu. Moreover, from the viewpoint of pattern formability and dimensional stability of the resulting pattern 3, it is preferable that the light-shielding pattern 1 and the pattern 3 contain the same kind of material. For example, it is more preferable that they contain the same metal element, and it is particularly preferable that they are the same metal or an alloy containing the same metal element.
[0315] A known method can be used as a method for forming the pattern 3 on the light-shielding pattern 1. The pattern 3 is preferably a pattern formed by a plating method. Known plating can be used as the plating. Examples of the plating include electroplating and electroless plating. The plating is preferably electroplating, and more preferably copper electroplating.
[0316] In electroplating, for example, a light-shielding pattern 1, which can function as a seed layer, can be used as a cathode, and a conductive pattern 3 can be formed on the light-shielding pattern 1 by stacking metal on top of the light-shielding pattern.
[0317] Examples of the components of the plating solution used in electroplating include water-soluble copper salts. As the water-soluble copper salt, water-soluble copper salts that are usually used as components of plating solutions can be used. As the water-soluble copper salt, it is preferable that the water-soluble copper salt is at least one selected from the group consisting of inorganic copper salts, copper salts of alkanesulfonic acids, copper salts of alkanolsulfonic acids, and copper salts of organic acids. Examples of the inorganic copper salts include copper sulfate, copper oxide, copper chloride, and copper carbonate. Examples of the copper salts of alkanesulfonic acids include copper methanesulfonate and copper propanesulfonate. Examples of the copper salts of alkanolsulfonic acids include copper isethionate and copper propanolsulfonate. Examples of the copper salts of organic acids include copper acetate, copper citrate, and copper tartrate.
[0318] The plating solution may contain sulfuric acid, which allows the pH and sulfate ion concentration of the plating solution to be adjusted.
[0319] The electroplating method and conditions are not limited. For example, the conductive pattern 3 can be formed on the light-shielding pattern 1 by supplying the transparent substrate after the development process to a plating tank containing a plating solution. In electroplating, the conductive pattern 3 can be formed by controlling, for example, the current density and the transport speed of the transparent substrate.
[0320] The temperature of the plating solution used in electroplating is generally 70° C. or less, and preferably 10° C. to 40° C. The current density in electroplating is generally 0.1 A / dm 2 ~100A / dm 2 and 0.5A / dm 2 ~20A / dm 2 It is preferable that the current density is increased to improve the productivity of the conductive pattern, and the current density is decreased to improve the uniformity of the thickness of the conductive pattern.
[0321] In the method of forming a conductive pattern 3 by plating, multiple metals may be plated continuously. For example, in the pattern 3 formed by a metal such as copper, the visibility or aesthetics may be deteriorated due to reflection. Methods for reducing the reflectance of the surface of the pattern 3 include, for example, oxidation treatment, sulfurization treatment, nitriding treatment, chlorination treatment, blackening layer film formation, and black plating. For example, a layer containing a black material can be formed on the surface of the pattern 3 by performing chrome plating after copper plating. The method for reducing the reflectance of the surface of the pattern 3 is preferably oxidation treatment or sulfurization treatment. Oxidation treatment can obtain a better anti-glare effect, and is also preferable in terms of ease of waste liquid treatment and environmental safety.
[0322] After the pattern 3 is formed, a post-baking process may be performed. The post-baking process can improve insulation reliability, curing characteristics, or plating adhesion by completely thermally curing unreacted thermosetting components. The heating temperature is preferably 80° C. to 240° C. The heating time is preferably 5 minutes to 120 minutes.
[0323] After the pattern 3 is formed, the surface of the pattern 3 may be protected by a resin layer. For example, after the pattern 3 is formed, a resin layer can be formed on the conductive pattern to protect the surface of the pattern 3. Examples of components of the resin layer include acrylic resin, polyester resin, polyvinyl acetal resin layer, polyimide resin, and epoxy resin. Examples of methods for forming the resin layer include coating and thermocompression bonding.
[0324] The structure of the pattern 3 may be a single-layer structure or a multi-layer structure. The components of each layer of the pattern 3 having a multi-layer structure may be the same or different.
[0325] The thickness of the pattern 3 is not limited. The thickness of the pattern 3 may be determined, for example, according to the application. When the pattern 3 is used as a wiring, the average thickness of the pattern 3 may be determined, for example, according to the magnitude of the current supplied to the wiring and the wiring width. From the viewpoint of electrical conductivity, the average thickness of the pattern 3 is preferably 0.5 μm or more, more preferably 1 μm or more, and particularly preferably 2 μm or more. Furthermore, the average thickness of the pattern 3 is preferably 3 μm or more, more preferably 5 μm or more, and particularly preferably 10 μm or more. The average thickness of the pattern 3 is measured by a method similar to the method for measuring the average thickness of the transparent substrate.
[0326] The width of the pattern 3 is preferably narrow. Specifically, the average width of the pattern 3 is preferably 50 μm or less, more preferably 10 μm or less, even more preferably 5 μm or less, and particularly preferably 2 μm or less. When the average width of the pattern 3 is 5 μm or less, the visibility of the pattern 3 in a device sensitive to visibility such as a touch panel can be reduced. From the viewpoint of electrical conductivity, the average width of the pattern 3 is preferably 0.1 μm or more, more preferably 0.5 μm or more, and particularly preferably 0.8 μm or more. The average width of the pattern 3 is measured by a method similar to the method for measuring the average width of the light-shielding pattern 1.
[0327] The surface resistance of the conductive pattern 3 is preferably less than 0.2 Ω / □, and more preferably less than 0.15 Ω / □. The surface resistance of the conductive pattern 3 is measured by a four-point probe method. When the pattern size is small and measurement is difficult, the surface resistance of a conductive layer of the same composition and thickness may be measured.
[0328] In the step of forming pattern 3, the interface between pattern 3 and light-shielding pattern 1 may not be clearly observed. For example, when light-shielding pattern 1 is used as a seed layer and pattern 3 is formed by plating, the interface between light-shielding pattern 1 and pattern 3 may not be clearly observed. However, the fact that the interface between pattern 3 and light-shielding pattern 1 is not clearly observed does not hinder the object of the present disclosure.
[0329] <Post-exposure process and post-heating process> The method for producing a structure according to the present disclosure preferably further includes a step of subjecting the resin pattern 2 to at least one of post-exposure and post-baking, from the viewpoint of improving the strength and durability of the resin pattern 2, which is a permanent film. The method for producing a structure according to the present disclosure preferably includes a step of post-exposing the resin pattern 2 after the development step (also referred to as a "post-exposure step"), and more preferably includes a step of post-exposing the resin pattern 2 after the pattern 3 formation step. Furthermore, the method for producing a structure according to the present disclosure may further include a step of heating (post-heating) the resin pattern 2 (also referred to as a "post-heating step"), if necessary. Since the resin pattern 2 is an exposed portion of the negative photosensitive resin layer N, by carrying out the post-exposure or post-heating, the remaining polymerization initiator, polymerizable compound, etc. further promote the polymerization reaction, etc., thereby improving the strength of the resin pattern 2 and its durability such as heat resistance, light resistance, and moisture resistance.
[0330] The light source used for exposure in the post-exposure step is not particularly limited, and a known exposure light source can be used. From the viewpoint of removability, it is preferable to use a light source containing light having the same wavelength as that in the resin pattern formation step.
[0331] The exposure dose in the post-exposure step is set to 5 mJ / cm from the viewpoint of removability. 2 ~5,000mJ / cm 2 and preferably 10 mJ / cm 2 ~3,000mJ / cm 2 More preferably, it is 100 mJ / cm 2 ~1,500mJ / cm 2 It is particularly preferred that:
[0332] From the viewpoint of removability, the exposure dose in the post-exposure step is preferably equal to or greater than the exposure dose in the resin pattern forming step, and more preferably greater than the exposure dose in the resin pattern forming step.
[0333] The method for producing a structure according to the present disclosure may include the post-heating step multiple times. The heating temperature and heating time in the post-heating step are not particularly limited and can be appropriately selected. The method of post-heating is not particularly limited, and a known method can be used. For example, the post-heating may be performed using a means provided in an exposure device and a development device, or may be performed using a hot plate or the like.
[0334] <Other processes> The method for producing a structure according to the present disclosure may include any steps (other steps) other than those described above. The other steps are not particularly limited, and may be any known steps. As examples of the resin pattern forming step and other steps in the present disclosure, the methods described in paragraphs 0035 to 0051 of JP-A No. 2006-23696 can also be suitably used in the present disclosure. The method for producing a structure according to the present disclosure may also include a step of polishing the obtained pattern, and a step of cleaning the obtained pattern. Furthermore, the method for manufacturing a structure according to the present disclosure may include a step of providing members according to each application, which will be described later.
[0335] <<Application>> The structure obtained by the method for producing a structure according to the present disclosure can be applied to various applications. Examples of applications of the structure obtained by the method for producing a structure according to the present disclosure include touch sensors, electromagnetic shields, antennas, wiring boards, and conductive heating elements. In the above applications, the structure obtained by the method for producing a structure according to the present disclosure can function as, for example, an electrical conductor. In addition, in the above applications, the structure obtained by the method for producing a structure according to the present disclosure can exhibit various functions depending on the properties of the formed patterns (resin pattern 2, pattern 3, etc.).
[0336] <Touch sensor> The touch sensor according to the present disclosure has a structure obtained by the method for producing a structure according to the present disclosure. In the touch sensor according to the present disclosure, the conductive pattern (for example, a light-shielding pattern 1 and a conductive pattern 3, etc., the same below) of the structure can be used as, for example, a transparent electrode or a frame wiring. The components of the touch sensor according to the present disclosure are not limited, except that the touch sensor includes a structure obtained by the method for producing a structure according to the present disclosure. As components other than the structure, components included in a known touch sensor can be used. The touch sensor is described in, for example, Japanese Patent No. 6486341 and Japanese Patent Laid-Open No. 2016-155978. The above publications are incorporated herein by reference. The method for producing a touch sensor according to the present disclosure is not limited as long as it is a method for producing a touch sensor having a structure obtained by the method for producing a structure according to the present disclosure.
[0337] <Electromagnetic wave shield> The electromagnetic shield according to the present disclosure has a structure obtained by the method for producing a structure according to the present disclosure. In the electromagnetic shield according to the present disclosure, the conductive pattern of the structure can be used, for example, as an electromagnetic shield. The components of the electromagnetic shield according to the present disclosure are not limited, except that the electromagnetic shield includes a structure obtained by the method for producing a structure according to the present disclosure. As components other than the structure, components included in known electromagnetic shields can be used. The electromagnetic shield is described, for example, in Japanese Patent No. 6486382 and Japanese Patent Laid-Open No. 2012-163951. The above publications are incorporated herein by reference. The method for producing the electromagnetic shield according to the present disclosure is not limited as long as it is a method for producing an electromagnetic shield having a structure obtained by the method for producing a structure according to the present disclosure.
[0338] <Antenna> The antenna according to the present disclosure is an antenna having a structure obtained by the method for producing a structure according to the present disclosure. In the antenna according to the present disclosure, the conductive pattern of the structure can be used, for example, as a transceiver or a transmission line. The components of the antenna according to the present disclosure are not limited, except that the antenna includes a structure obtained by the method for producing a structure according to the present disclosure. As components other than the structure, components included in a known antenna can be used. The antenna is described, for example, in JP 2016-219999 A. The above publication is incorporated herein by reference. The method for producing the antenna according to the present disclosure is not limited as long as it is a method for producing an antenna having a structure obtained by the method for producing a structure according to the present disclosure.
[0339] <Wiring board> The wiring board according to the present disclosure has a structure obtained by the method for producing a structure according to the present disclosure. In the wiring board according to the present disclosure, the conductive pattern of the structure can be used, for example, as wiring of a printed wiring board. The components of the wiring board according to the present disclosure are not limited, except that they include a structure obtained by the method for producing a structure according to the present disclosure. As components other than the above structure, components included in a known wiring board can be used. The wiring board is described, for example, in Japanese Patent No. 5774686 and Japanese Patent Laid-Open No. 2017-204538. The above publications are incorporated herein by reference. The method for producing the wiring board according to the present disclosure is not limited as long as it is a method for producing a wiring board having a structure obtained by the method for producing a structure according to the present disclosure.
[0340] <Conductive heating element> The conductive heating element according to the present disclosure has a structure obtained by the method for producing a structure according to the present disclosure. In the conductive heating element according to the present disclosure, the conductive pattern of the structure can be used, for example, as a heating element. The components of the conductive heating element according to the present disclosure are not limited, except that they include a structure obtained by the method for producing a structure according to the present disclosure. As components other than the structure, components included in a known conductive heating element can be used. The conductive heating element is described, for example, in Japanese Patent Publication No. 6486382. The above publication is incorporated herein by reference. The method for producing the conductive heating element according to the present disclosure is not limited as long as it is a method for producing a conductive heating element having a structure obtained by the method for producing a structure according to the present disclosure.
[0341] (structure) The structure according to the present disclosure has a transparent substrate, a light-shielding pattern 1 arranged on the transparent substrate, a resin pattern 2 arranged on the transparent substrate adjacent to the light-shielding pattern 1 and in contact with the transparent substrate, and a pattern 3 in a region defined by the light-shielding pattern 1 and the resin pattern 2, the light-shielding pattern 1 has an average thickness of 2 μm or less, the resin pattern 2 has an average thickness of more than 2 μm, the pattern 3 has an average thickness greater than the average thickness of the light-shielding pattern 1, and the resin pattern 2 is a permanent film. According to the above aspect, a structure having a conductive pattern with reduced occurrence of morphological abnormalities is provided. Moreover, the structure according to the present disclosure is preferably a structure manufactured by the method for manufacturing a structure according to the present disclosure.
[0342] Except for the above, preferred aspects of the transparent substrate, light-shielding pattern 1, resin pattern 2, and pattern 3 in the structure according to the present disclosure are the same as the preferred aspects of the transparent substrate, light-shielding pattern 1, resin pattern 2, and pattern 3 in the manufacturing method for a structure according to the present disclosure described above.
[0343] The structure A according to the present disclosure will be described with reference to FIG. 2. FIG. 2 is a schematic cross-sectional view showing an example of the structure according to the present disclosure. The structure 200 shown in FIG. 2 has a transparent substrate 11, a pattern 21 (light-shielding pattern 1), a resin pattern 41 (resin pattern 2), and a pattern 51 (pattern 3). The light-shielding pattern 21 is disposed on the transparent substrate 11. The light-shielding pattern 21 is in contact with the transparent substrate 11. However, the light-shielding pattern 21 may be in contact with the transparent substrate 11 via another layer (not shown). The resin pattern 41 is disposed next to the light-shielding pattern 21 on the transparent substrate 11 and in contact with the transparent substrate 11. The pattern 51 is disposed on the light-shielding pattern 21 and between the resin patterns 41. EXAMPLES
[0344] The present disclosure will be described in detail below with reference to examples, but the present disclosure is not limited to the following examples.
[0345] <Synthesis of tetrahydrofuran-2-yl acrylate (ATHF)> Acrylic acid (72.1 g, 1.0 mol) and hexane (72.1 g) were added to a three-neck flask and cooled to 20° C. Camphorsulfonic acid (7.0 mg, 0.03 mmol) and 2-dihydrofuran (77.9 g, 1.0 mol) were added dropwise, and the mixture was stirred at 20° C.±2° C. for 1.5 hours, then heated to 35° C. and stirred for 2 hours. Kyoward 200 (filter material, aluminum hydroxide powder, manufactured by Kyowa Chemical Industry Co., Ltd.) and Kyoward 1000 (filter material, hydrotalcite powder, manufactured by Kyowa Chemical Industry Co., Ltd.) were laid in a Nutsche in this order, and the reaction liquid was filtered to obtain a filtrate. Hydroquinone monomethyl ether (MEHQ, 1.2 mg) was added to the obtained filtrate, and the mixture was concentrated under reduced pressure at 40° C. to obtain 140.8 g of tetrahydrofuran-2-yl acrylate (ATHF) as a colorless oil (yield 99.0%).
[0346] <Synthesis of Polymer A-1> PGMEA (75.0 g) was placed in a three-neck flask and heated to 90 ° C. under a nitrogen atmosphere. A solution containing ATHF (40.0 g), AA (2.0 g), EA (20.0 g), MMA (22.0 g), CHA (16.0 g), V-601 (4.0 g), and PGMEA (75.0 g) was added dropwise to the three-neck flask solution maintained at 90 ° C. ± 2 ° C. over 2 hours. After the addition, the mixture was stirred at 90 ° C. ± 2 ° C. for 2 hours to obtain polymer A-1 (solid content concentration 40.0 mass %). The content of each structural unit in polymer A-1 is shown in Table 1. The acid value of polymer A-1 is 15.6 mg KOH / g. The above abbreviations represent the following compounds, respectively. "AA": Acrylic acid (Tokyo Chemical Industry Co., Ltd.) "CHA": Cyclohexyl acrylate (Tokyo Chemical Industry Co., Ltd.) "EA": Ethyl acrylate (Tokyo Chemical Industry Co., Ltd.) "MMA": Methyl methacrylate (Tokyo Chemical Industry Co., Ltd.) "PGMEA": Propylene glycol monomethyl ether acetate (manufactured by Showa Denko K.K.) "V-601": 2,2'-azobis(2-methylpropionate)dimethyl (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)
[0347] <Synthesis of Polymer A-2> A solution containing polymer A-2 (solid content concentration: 40.0% by mass) was obtained in the same manner as for polymer A-1, except that the amounts of monomers used were changed as follows: The weight average molecular weight of polymer A-2 was 60,000. (1) Styrene: 52.0 g (2) Methacrylic acid: 29.0 g (3) Methyl methacrylate: 19.0 g
[0348] <Synthesis of Polymer A-3> A solution containing polymer A-3 (solid content concentration: 40.0 mass%) was obtained in the same manner as polymer A-1, except that the monomers (styrene, methacrylic acid, and methyl methacrylate) used in the synthesis of polymer A-1 were changed to the following monomers. The weight average molecular weight of polymer A-3 was 40,000. (1) Benzyl methacrylate: 81.0 g (2) Methacrylic acid: 19.0 g
[0349] <Preparation of negative type photosensitive resin composition> Components selected according to the description in Table 1 were mixed, and then methyl ethyl ketone was added to prepare negative photosensitive resin compositions NR1 to NR6 (solid content concentration: 25% by mass).
[0350] [Table 1]
[0351] The units of values in the component columns in Table 1 are parts by mass. Details of the abbreviations used in Table 1 are shown below. BPE-500: Ethoxylated bisphenol A dimethacrylate (10 moles of ethylene oxide added), manufactured by Shin-Nakamura Chemical Co., Ltd. BPE-200: Ethoxylated bisphenol A dimethacrylate (4 moles of ethylene oxide added), manufactured by Shin-Nakamura Chemical Co., Ltd. M-270: Polypropylene glycol diacrylate, manufactured by Toagosei Co., Ltd. A-TMPT: Trimethylolpropane triacrylate, manufactured by Shin-Nakamura Chemical Co., Ltd. SR-454: Ethoxylated trimethylolpropane triacrylate (3 moles of ethylene oxide added), manufactured by Arkema SR-502: Ethoxylated trimethylolpropane triacrylate (9 moles of ethylene oxide added), manufactured by Arkema A-9300-CL1: ε-caprolactone modified tris-(2-acryloxyethyl) isocyanurate, manufactured by Shin-Nakamura Chemical Co., Ltd. B-CIM: Photoradical generator (photopolymerization initiator), manufactured by Hampford, 2-(2-chlorophenyl)-4,5-diphenylimidazole dimer SB-PI 701: Sensitizer, 4,4'-bis(diethylamino)benzophenone, manufactured by Sanyo Trading Co., Ltd. CBT-1: Rust inhibitor, carboxybenzotriazole, manufactured by Johoku Chemical Industry Co., Ltd. TDP-G: Polymerization inhibitor, phenothiazine, Kawaguchi Chemical Industry Co., Ltd. Irganox245: Polymerization inhibitor, hindered phenol compound, manufactured by BASF F-552: Fluorosurfactant, Megafac F552, manufactured by DIC Corporation
[0352] <Preparation of positive-type photosensitive resin composition PR1> Polymer A-1, photoacid generator B-1, surfactant C-1, and basic compound D-1, which were weighed according to the composition shown in Table 2 below, were mixed with PGMEA to obtain a mixture with a solid content concentration of 10% by mass. The mixture was filtered using a polytetrafluoroethylene filter with a pore size of 0.2 μm to obtain a positive photosensitive resin composition PR1.
[0353] [Table 2]
[0354] The units of the numerical values in the column for each component in Table 2 are parts by mass. In addition, details of each component other than those mentioned above in Table 2 are shown below.
[0355] Photoacid generator B-1 is a compound having the following structure (the compound described in paragraph 0227 of JP2013-47765A, and was synthesized according to the method described in paragraph 0227).
[0356] [ka]
[0357] Surfactant C-1 is a compound having the following structure:
[0358] [ka]
[0359] The basic compound D-1 is a compound having the following structure:
[0360] [ka]
[0361] <Preparation of negative type photosensitive resin compositions N1 to N8> Negative photosensitive resin compositions N1 to N8 (solid content concentration: 29 mass%) were prepared by mixing the components selected according to the description in Table 3 or Table 4, and then adding a 1:1 (mass ratio) mixed solvent of 1-methoxy-2-propyl acetate and methyl ethyl ketone.
[0362] [Table 3]
[0363] [Table 4]
[0364] The unit of the content of each component in Tables 3 and 4 is parts by mass. Moreover, details of each component listed in Table 3 are shown below. - Ethylenically unsaturated compounds - M-1: A-NOD-N (1,9-nonanediol diacrylate, manufactured by Shin-Nakamura Chemical Co., Ltd.) M-2: Dipentaerythritol hexaacrylate (A-DPH, manufactured by Shin-Nakamura Chemical Co., Ltd.) M-3: A-DCP (tricyclodecane dimethanol diacrylate, manufactured by Shin-Nakamura Chemical Co., Ltd.) M-4: Aronix TO-2349 (a polyfunctional ethylenically unsaturated compound having a carboxylic acid group, manufactured by Toagosei Co., Ltd.) M-5: Urethane acrylate 8UX-015A (manufactured by Taisei Fine Chemical Co., Ltd.)
[0365] -Alkali-soluble polymer- P-1: Resin shown below, styrene-derived structural unit (St) / dicyclopentanyl methacrylate-derived structural unit (DCPMA) / methacrylic acid-derived structural unit (MAA) / structural unit obtained by adding glycidyl methacrylate to a methacrylic acid-derived structural unit (GMA-MAA)=41.0 / 15.2 / 23.9 / 19.9 (mol%), Mw=17,000)
[0366] -Photopolymerization initiator- D-1: 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone-1-(O-acetyloxime) (Irgacure OXE-02, manufactured by BASF) D-2: 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one (Irgacure 907, manufactured by BASF) D-3: B-CIM (photoradical generator (photopolymerization initiator), manufactured by Hampford, 2-(2-chlorophenyl)-4,5-diphenylimidazole dimer): 0.89 parts by mass
[0367] -Thermal crosslinkable compound- E-1: Duranate WT32-B75P (blocked isocyanate compound, manufactured by Asahi Kasei Chemicals Corporation): 12.50 parts
[0368] -Other ingredients- AD-1: Hydrogen donor compound (N-phenylglycine, Junsei Chemical Co., Ltd.) AD-2: Styrene / maleic anhydride copolymer (4:1 molar ratio) (AD-2, SMA EF-40, acid anhydride value 1.94 mmol / g, weight average molecular weight 10,500, Cray Valley) AD-3: Fluorine-based surfactant (Megafac F551A, manufactured by DIC Corporation) AD-4: Sensitizer (4,4'-bis(diethylamino)benzophenone, SB-PI 701, Sanyo Trading Co., Ltd.) AD-5: Dye (Leuco Crystal Violet, Yamada Chemical Industries Co., Ltd.) AD-6: Polymerization inhibitor (phenothiazine, Kawaguchi Chemical Industry Co., Ltd. TDP-G) AD-7: Rust inhibitor (carboxybenzotriazole, CBT-1 manufactured by Johoku Chemical Industry Co., Ltd.) AD-8: Fluorosurfactant (Megafac F552, manufactured by DIC Corporation)
[0369] Example 1 <Preparation of photosensitive transfer material (dry film) 1> A PET film (Lumirror 16KS40 manufactured by Toray Industries, Inc., thickness: 16 μm: arithmetic average roughness Ra: 0.02 μm) was prepared as a temporary support. The negative photosensitive resin composition NR1 was applied to the surface of the temporary support using a slit nozzle so that the application width was 1.0 m and the thickness after drying was the value listed in Table 5. The coating film of the negative photosensitive resin composition NR1 formed was dried at 90 ° C. for 100 seconds to form a resist layer. A polyethylene film (Tamapoly Co., Ltd., GF-818, thickness: 19 μm) was pressed onto the surface of the formed resist layer as a cover film to produce a photosensitive transfer material 1. The obtained photosensitive transfer material 1 was wound up to produce a roll-shaped photosensitive transfer material 1.
[0370] <Formation of light-shielding pattern 1 (copper pattern)> A copper layer having a thickness of 0.05 μm was formed by sputtering on a polyethylene terephthalate (PET) film having a thickness of 100 μm, to prepare a PET film with a copper layer. After peeling off the cover film from the photosensitive transfer material 1, the photosensitive transfer material 1 was laminated to the PET film with the copper layer. The lamination process was carried out under the conditions of a roll temperature of 100° C., a linear pressure of 1.0 MPa, and a linear speed of 1.0 m / min. Next, the resist layer was exposed to light by using a high-pressure mercury lamp exposure machine (MAP-1200L, manufactured by Dainihon Kaken Co., Ltd., main wavelength: 365 nm) through a photomask. After peeling off the temporary support, the resist layer was shower-developed for 30 seconds using an aqueous sodium carbonate solution having a liquid temperature of 25° C. to form a resin pattern (line / space=5.5 μm / 4.5 μm). The copper layer not covered with the resin pattern was etched using an etching solution (Cu-02, manufactured by Kanto Chemical Co., Ltd.). The remaining resin pattern was removed using a stripping solution (10% by mass sodium hydroxide aqueous solution). By the above procedure, a PET film with a copper pattern (line / space = 5 μm / 5 μm) was produced. The copper pattern functions as light-shielding pattern 1. The average thickness of light-shielding pattern 1 is shown in Table 5.
[0371] <Preparation of Photosensitive Transfer Material 2> A PET film (Lumirror 16KS40 manufactured by Toray Industries, Inc., thickness: 16 μm, arithmetic mean roughness Ra: 0.02 μm) was prepared as a temporary support. Negative photosensitive resin composition N1 was applied to the surface of the temporary support using a slit nozzle so that the application width was 1.0 m and the thickness after drying was the value shown in Table 5. The formed coating film of negative photosensitive resin composition N1 was dried at 90° C. for 100 seconds.
[0372] Thereafter, a polyethylene film (Tamapoly Corporation, GF-818, thickness: 19 μm) was pressed as a cover film to produce a photosensitive transfer material 2. The obtained photosensitive transfer material 2 was wound up to produce a roll of the photosensitive transfer material 2.
[0373] <Formation of Pattern 3 (Copper Pattern)> After peeling off the cover film from the photosensitive transfer material 2, the PET film with the copper pattern and the photosensitive transfer material 2 were laminated together. The lamination process was carried out under conditions of a roll temperature of 100°C, a linear pressure of 1.0 MPa, and a linear speed of 1.0 m / min. The obtained laminate had a PET film, a copper pattern (light-shielding pattern 1), a negative photosensitive resin layer N, and a temporary support in this order. The surface of the PET film opposite to the surface facing the copper pattern (light-shielding pattern 1) was irradiated with light using a high-pressure mercury lamp exposure machine (MAP-1200L, manufactured by Dainihon Kaken Co., Ltd., main wavelength: 365 nm). The exposure dose was 70 mJ / cm. 2After peeling off the temporary support, the negative photosensitive resin layer N was shower-developed for 30 seconds using an aqueous sodium carbonate solution at a liquid temperature of 25°C to form a resin pattern 2. The space portion (i.e., the groove) of the copper pattern (light-shielding pattern 1) was filled with the resin pattern 2. The average thickness of the resin pattern 2 is shown in Table 2. Copper was deposited by electrolytic copper plating on the copper pattern (light-shielding pattern 1) that was not covered with the resin pattern 2 to form a conductive pattern 3. The current density in the electrolytic copper plating was 1.8 ASD. The treatment time in the electrolytic copper plating was 6 minutes. The PET film after the electrolytic copper plating was heated at 130°C for 30 minutes. A structure having a copper pattern (line (L) / space (S)=5 μm / 5 μm) was produced by the above procedure. The average thickness of the copper pattern (conductive pattern 3) deposited by electrolytic copper plating is shown in Table 5.
[0374] (Examples 2 to 13) The type and thickness of the substrate, the thickness (average thickness) of the light-shielding pattern 1, the type of the photosensitive resin composition forming the light-shielding pattern 1, the dry coating thickness of the photosensitive resin composition (thickness of the resist layer), the shape of the light-shielding pattern 1, the exposure method when forming the photosensitive pattern 1 (including the presence or absence of peeling of the temporary support), the method for forming the negative photosensitive resin layer N and the negative photosensitive composition used, the type of other layers, the thickness (average thickness) of the pattern 3, and the presence or absence of the curing treatment were appropriately changed according to the description in Table 5. A structure having a copper pattern was produced by the same procedure as in Example 1. The average thickness of the copper deposited by electrolytic copper plating can be increased by extending the treatment time.
[0375] In Example 2, a polyimide (PI) film having a thickness of 100 μm was used as the substrate, and after forming the pattern 3, a high-pressure mercury lamp exposure machine (MAP-1200L manufactured by Nippon Kaken Co., Ltd., main wavelength: 365 nm) was used to expose the film to 1,000 mJ / cm 2 The film was then post-exposed by irradiating the film with light in an amount of 1000 x 100
[0376] In Example 3, the substrate used was a substrate (COP / ITO) in which a 0.1 μm-thick indium tin oxide (ITO) film was formed by sputtering on a 100 μm-thick polycycloolefin (COP) film, and a 0.03 μm-thick copper layer was formed by sputtering on the substrate, thereby preparing a substrate with a copper layer. In Example 3, instead of the negative type photosensitive resin composition N1, N10 was formed by laminating a high refractive index layer on the following negative type photosensitive resin composition N1. A PET film (Lumirror 16KS40 manufactured by Toray Industries, Inc., thickness: 16 μm, arithmetic mean roughness Ra: 0.02 μm) was prepared as a temporary support. The negative photosensitive resin composition N1 was applied to the surface of the temporary support using a slit nozzle so that the application width was 1.0 m and the thickness after drying was 3 μm. The formed coating film of the negative photosensitive resin composition N1 was dried at 90° C. for 100 seconds to form a negative photosensitive resin layer N. Next, on the negative photosensitive resin layer N, a coating solution for an overcoat layer (composition N9) having the following formulation 201 was applied using a slit nozzle so as to have a thickness of 0.2 μm after drying, and the solvent was removed by drying in a hot air convection dryer having a temperature gradient of 40° C. to 95° C. to form an overcoat layer (OC layer) disposed directly in contact with the photosensitive layer. The refractive index of the overcoat layer was 1.68 at a wavelength of 550 nm at 25° C. Here, formulation 201 was prepared using a resin having an acid group and an aqueous ammonia solution, and the resin having an acid group was neutralized with the aqueous ammonia solution to prepare a coating liquid for an overcoat layer, which was an aqueous resin composition containing an ammonium salt of the resin having an acid group.
[0377] - Overcoat coating solution: Formulation 201 (water-based resin composition) - Acrylic resin (ZB-015M, Fujifilm Fine Chemicals Co., Ltd., copolymer resin of methacrylic acid / allyl methacrylate, weight average molecular weight 25,000, composition ratio (molar ratio) = 20 / 80, solid content 5.00%, aqueous ammonia solution): 4.92 parts Polyfunctional ethylenically unsaturated compound having a carboxylic acid group (Aronix TO-2349, manufactured by Toagosei Co., Ltd.): 0.04 parts ZrO2 particles (Nanouse OZ-S30M, solid content 30.5%, methanol 69.5%, refractive index 2.2, average particle size: approx. 12 nm, manufactured by Nissan Chemical Industries, Ltd.): 4.34 parts Rust inhibitor (benzotriazole derivative, BT-LX, manufactured by Johoku Chemical Industry Co., Ltd.): 0.03 parts Surfactant (fluorosurfactant, Megafac F444, manufactured by DIC Corporation): 0.01 part Distilled water: 24.83 parts Methanol: 65.83 parts
[0378] A polyethylene film (manufactured by Tamapoly Co., Ltd., GF-818, thickness: 19 μm) was pressure-bonded as a cover film to the surface of the formed overcoat layer to produce a photosensitive transfer material 2. The obtained photosensitive transfer material 2 was wound up to produce a roll-shaped photosensitive transfer material 2.
[0379] In Example 4, exposure was performed by a direct imaging exposure (DI exposure) method using a direct imaging exposure device (DE-1DH, manufactured by Via Mechanics Co., Ltd., dominant wavelength 405 nm). Furthermore, in Example 7, the substrate laminated with the photosensitive transfer material was fixed onto a 4-inch silicon wafer with tape, and then reduced projection exposure was performed using an i-line stepper (NSR-2009i9C) manufactured by Nikon Corporation. Furthermore, after forming pattern 3, heating was performed at 145°C for 20 minutes. In addition, in Examples 9 and 10, the photosensitive transfer material 1 was not used, and the positive photosensitive resin composition PR1 shown in Table 5 was applied and dried at 90°C for 100 seconds to form a resist layer having the thickness shown in Table 5. Furthermore, in Examples 8 and 11, the photosensitive transfer material 2 was not used, and the negative photosensitive resin composition shown in Table 5 was applied and dried at 90°C for 100 seconds to form a negative photosensitive resin layer N having the thickness shown in Table 5.
[0380] In Example 12, the light-shielding pattern 1 was formed as follows. A PET film (Cosmoshine A4300, manufactured by Toyobo Co., Ltd., thickness: 75 μm) was prepared. A monochrome inkjet printer PX-K100 (manufactured by Seiko Epson Corporation) was prepared by transferring the ink in the ink cartridge to silver nano-ink (DryCure Ag-J, manufactured by C-INK Co., Ltd.). A wiring pattern was formed by printing the ink on this printer via a printer driver, and then the printer was heated at 60°C for 2 minutes. A PET film with a silver wiring pattern (line / space = 50 μm / 50 μm) was produced. After the resin pattern 2 was formed, the copper pattern 3 was formed as follows. A Cu plating bath was prepared using electroless copper plating solution (ARG Copper, manufactured by Okuno Chemical Industries Co., Ltd.) according to the procedure described in the instruction manual, and then placed in a thermostatic chamber at 45°C to regulate the temperature. A substrate was immersed in the plating bath to form a copper pattern by electroless plating.
[0381] In Example 13, the light-shielding pattern 1 was formed as follows. After peeling off the cover film from the photosensitive transfer material 1 onto a 100 μm thick polyimide (PI) film, the photosensitive transfer material 1 was laminated onto the PET film with the copper layer. The above lamination was performed under conditions of a roll temperature of 100° C., a linear pressure of 1.0 MPa, and a linear speed of 1.0 m / min. Next, the resist layer was exposed to light using a maskless lithography device (Heidelberg DWL66+, main wavelength: 405 nm). After peeling off the temporary support, the resist layer was shower-developed for 30 seconds using an aqueous sodium carbonate solution with a liquid temperature of 25° C. to form a resin pattern (line / space=15 μm / 15 μm). Next, a copper layer was formed between the resist patterns and on the resist pattern by sputtering, and then the copper layer on the resin pattern and the resin pattern was removed using a stripping solution (10% by mass triethylamine aqueous solution). Through the above procedure, a PI film with a copper pattern (line / space=15 μm / 15 μm) was produced. The copper pattern functions as a light-shielding pattern 1 . Other operations were the same as in Example 1, except that in developing the resin pattern 2, a 2.38 mass % aqueous solution of tetramethylammonium hydroxide (TMAH) was used as the developer.
[0382] Comparative Example 1 In the step described in the section "Formation of Pattern 3 (Copper Pattern)", except that the light irradiation method was changed, a structure having a copper pattern was produced by the same procedure as in Example 1. Specifically, in a laminate having a PET film, a copper pattern (light-shielding pattern), a negative photosensitive resin layer N, and a temporary support in this order, a photomask was brought into contact with the surface of the temporary support opposite to the surface on which the negative photosensitive resin layer N was arranged, and then the negative photosensitive resin layer N was irradiated with light through the photomask. However, in the step of irradiating light, a positional shift of the copper pattern (light-shielding pattern) that was thought to have occurred due to the shrinkage of the PET film was observed, so it was difficult to align the position of the opening of the photomask with the space portion of the copper pattern (light-shielding pattern). As a result, a resin pattern could not be formed in the space portion of the copper pattern (light-shielding pattern).
[0383] <Evaluation> [Pattern formation] Using an optical microscope, 100 random fields of view of the obtained structure having pattern 3 were observed. The range of each field of view was 200 μm × 200 μm. Based on the number of fields in which abnormalities were observed in pattern 3, the formability of the conductive pattern was evaluated according to the following criteria. An abnormality refers to a portion in pattern 3 where morphological abnormalities such as cracks, peeling, and chipping were observed. The evaluation results are shown in Table 5. A: The number of visual fields in which abnormal areas were observed was less than 20. B: Abnormal areas were observed in 20 or more visual fields.
[0384] [Table 5]
[0385] In addition, N9 in the column of the negative photosensitive composition used in Example 3 of Table 5 indicates the overcoat coating liquid (composition N9). The results shown in Table 5 show that the methods for manufacturing the structures of Examples 1 to 13 are capable of forming patterns with reduced occurrence of morphological abnormalities, as compared with the method for manufacturing the structure of Comparative Example 1.
[0386] The disclosure of Japanese Patent Application No. 2020-080716, filed on April 30, 2020, is incorporated herein by reference in its entirety. All publications, patent applications, and standards mentioned in this specification are herein incorporated by reference to the same extent as if each individual publication, patent application, or standard was specifically and individually indicated to be incorporated by reference. [Explanation of symbols]
[0387] 10,11: Transparent base material 10a: Exposed surface 20, 21: Light-shielding pattern (light-shielding pattern 1) 30: Negative photosensitive resin layer (negative photosensitive resin layer N) 30a: Exposure section 40, 41: Resin pattern (Resin pattern 2) 50,51:Pattern (Pattern 3) 100: Laminate 200: Structure
Claims
1. A step of preparing a laminate including a transparent substrate, a light-shielding pattern 1 disposed on the transparent substrate, and a negative-type photosensitive resin layer N disposed on the transparent substrate and the light-shielding pattern 1 and in contact with the transparent substrate; a step of irradiating a part of the negative type photosensitive resin layer N with light from a surface of the transparent base material opposite to a surface on which the light-shielding pattern 1 is provided; a step of developing the negative photosensitive resin layer N irradiated with light to form a resin pattern 2 on the transparent substrate; and forming a pattern 3 in an area defined by the light-shielding pattern 1 and the resin pattern 2; The resulting structure has the resin pattern 2 as a permanent film, The negative photosensitive resin layer N is made of a negative photosensitive resin composition containing, as a polymerizable compound, a di(meth)acrylate compound having a dicyclopentanyl structure or a dicyclopentenyl structure, which is an aliphatic cyclic skeleton, an alkali-soluble polymer, and a photopolymerization initiator. A method for manufacturing a structure.
2. A step of preparing a laminate including a transparent substrate, a light-shielding pattern 1 disposed on the transparent substrate, and a negative-type photosensitive resin layer N disposed on the transparent substrate and the light-shielding pattern 1 and in contact with the transparent substrate; a step of irradiating a part of the negative type photosensitive resin layer N with light from a surface of the transparent base material opposite to a surface on which the light-shielding pattern 1 is provided; a step of developing the negative photosensitive resin layer N irradiated with light to form a resin pattern 2 on the transparent substrate; and forming a pattern 3 in an area defined by the light-shielding pattern 1 and the resin pattern 2; The resulting structure has the resin pattern 2 as a permanent film, The negative photosensitive resin layer N is made of a negative photosensitive resin composition containing a polyfunctional epoxy resin, a hydroxyl group-containing compound, and a photocationic polymerization initiator. A method for manufacturing a structure.
3. The method for manufacturing a structure according to claim 1 or 2, wherein the light-shielding pattern 1 contains a metal.
4. The method for producing a structure according to any one of claims 1 to 3, wherein the pattern 3 has electrical conductivity.
5. The method for producing a structure according to any one of claims 1 to 4, wherein the pattern 3 is a pattern formed by a plating method.
6. 6. The method for manufacturing a structure according to claim 1, wherein the light-shielding pattern 1 and the pattern 3 contain the same type of material.
7. The method for producing a structure according to any one of claims 1 to 6, wherein the negative photosensitive resin layer N contains a metal oxidation inhibitor.
8. A step of forming a light-shielding layer on one surface of a transparent substrate; forming a photoresist layer on the light-shielding layer; exposing and developing the photoresist layer to form a resist pattern; and The method for producing the structure according to any one of claims 1 to 7, further comprising the step of etching the light-shielding layer to form the light-shielding pattern 1.
9. 9. The method for manufacturing a structure according to claim 1, wherein an average thickness of the light-shielding pattern 1 is greater than an average thickness of the pattern 3.
10. The method for producing a structure according to any one of claims 1 to 9, wherein the transparent substrate is a transparent film substrate.
11. The method for producing the structure according to any one of claims 1 to 10, further comprising the step of subjecting the resin pattern (2) to at least one of post-exposure and post-baking.
12. The method for producing a structure according to any one of claims 1 to 11, wherein the negative photosensitive resin layer N is a layer formed from a photosensitive transfer material.
13. The method for producing a structure according to any one of claims 1 to 12, wherein the obtained structure is one structure selected from the group consisting of a touch sensor, an electromagnetic wave shield, an antenna, a wiring board, a conductive heating element, and a viewing angle control film.
Citation Information
Patent Citations
Manufacture of high density printed wiring board
JP1993183259A
Freeze-dried bean curd and production thereof
JP1995031399A
Insulation resin composition and production of multilayer printed wiring board prepared by using same
JP2000186217A
Method for forming metal pattern
JP2000265087A
Printed wiring board and method for manufacturing the same
JP2010267652A